Method for manufacturing plastic lens

By forming a SiO primer layer and an optically functional layer on a thermoplastic acrylic resin substrate through a specific process, the problems of low adhesion and productivity are resolved, resulting in a method for manufacturing plastic lenses with high durability and efficient production, suitable for applications in harsh environments.

CN120776245APending Publication Date: 2025-10-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510408764.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-02-26
Filing Date
2025-04-02
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

In the existing technology, the acrylic resin base has poor adhesion and production efficiency, the existing technology cannot effectively solve the problems of adhesion and production efficiency of plastic lenses, and the existing technology cannot effectively solve the problems of low productivity in the manufacturing method of plastic lenses. In the existing technology, the resistance heating vacuum evaporation method and the wet film forming method are difficult to balance adhesion and shape accuracy, and cannot meet the requirements of durability and productivity.

Method used

Using a thermoplastic acrylic resin as the substrate, a SiO primer layer is formed by a resistance heating vacuum evaporation method under a specific oxygen level. Subsequently, an electron beam heating vacuum evaporation method is used to form an optical functional layer. The thickness of the primer layer and the optical functional layer and the pre-melting process are controlled to ensure adhesion and production efficiency.

Benefits of technology

The improved adhesion and productivity of plastic lenses meet durability requirements and are suitable for applications in harsh environments, especially components such as automotive cameras.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120776245A_ABST
    Figure CN120776245A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a method for producing a plastic lens having excellent adhesion and productivity of an optical functional layer and further improved durability. The present invention provides a method for manufacturing a plastic lens, which comprises a formation step for sequentially forming an undercoat layer and an optical functional layer on at least one surface of a resin lens body, and which is characterized in that: the lens body is composed of a thermoplastic acrylic resin having a glass transition temperature of 116 DEG C or more; the undercoat layer is formed by a resistance heating type vacuum vapor deposition method, SiO is used as a vapor deposition material of the undercoat layer, and the amount of oxygen is controlled at a pressure of less than 3.0 * 10 <-2 > Pa, the optical functional layer is formed by an electron beam heating type vacuum vapor deposition method, and the vapor deposition material of the optical functional layer is pre-melted before and after the formation of the undercoat layer.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a method for manufacturing a plastic lens. BACKGROUND

[0002] Acrylic resins typified by polymethyl methacrylate (PMMA) are used as optical materials and the like from the viewpoints of high transparency, low birefringence, light stability, and the like. For example, a plastic lens in which a antireflection layer is formed on the surface of a PMMA substrate is disclosed in Patent Literature 1.

[0003] In recent years, however, acrylic resins having excellent heat resistance have been developed from the demand for use of the acrylic resins in harsh environments such as high temperature and high humidity and in parts such as monitoring cameras and vehicle-mounted cameras that require more durable quality than ever before. For example, a plastic lens using an acrylic resin having excellent heat resistance as a substrate is disclosed in Patent Literature 2.

[0004] PRIOR ART DOCUMENTS

[0005] Patent Literature 1: Japanese Patent Application Laid-Open No. 6-273601

[0006] Patent Literature 2: International Publication No. 2023 / 074597 SUMMARY

[0007] As a film forming method for forming an optical functional layer (antireflection layer, partial reflection layer, and the like) on a resin substrate, a vacuum evaporation method (dry film forming method) using electron beam heating is used in many cases, but it is generally known that when the substrate is an acrylic resin, it is difficult to obtain good adhesion by this method. In view of this problem, in the plastic lens described in Patent Literature 1, a primer layer mainly composed of silicon oxide is formed between the PMMA substrate and the antireflection layer by a vacuum evaporation method using resistance heating to improve adhesion. However, the results of research by the present inventors and others have shown that peeling easily occurs depending on the formation conditions of the antireflection layer even when a primer layer is formed by the method described in Patent Literature 1. In addition, the PMMA substrate of this plastic lens has low heat resistance, and thus there is a problem in that it cannot sufficiently cope with the durability quality required for vehicle-mounted cameras and the like.

[0008] On the other hand, in the plastic lens described in Patent Literature 2, a hard coat layer is formed between the substrate composed of an acrylic resin and the antireflection layer by a wet film forming method to improve adhesion. However, the shape accuracy of the film forming surface is much poorer when a wet film forming method is employed than when a dry film forming method is employed, and thus this method cannot cope with applications that require high control of the surface shape. In addition, coating, drying, and curing processes of the hard coat layer are required between the molding process of the lens substrate and the film forming process of the antireflection layer, and thus there is also a problem in that the productivity is poor.

[0009] Accordingly, an object of the present application is to provide a plastic lens manufacturing method that is excellent in adhesion of an optical functional layer and productivity and further improves durability.

[0010] That is, the present application is as follows.

[0011] [1] A plastic lens manufacturing method including a forming step of sequentially forming a primer layer and an optical functional layer on at least one face of a lens main body made of resin, characterized in that the lens main body is composed of a thermoplastic acrylic resin having a glass transition temperature of 116°C or higher, the primer layer is formed by a vacuum evaporation method of a resistance heating type, SiO is used as an evaporation material of the primer layer, an amount of oxygen is controlled to be less than 3.0 x 10 -2 Pa, and the optical functional layer is formed by a vacuum evaporation method of an electron beam heating type, pre-melting of an evaporation material of the optical functional layer is performed before and after formation of the primer layer.

[0012] [2] The plastic lens manufacturing method according to [1], characterized in that the pre-melting before formation of the primer layer is performed in a state where the lens is not disposed in an evaporation device.

[0013] [3] The plastic lens manufacturing method according to [2], characterized in that, after formation of the primer layer, pre-melting of a meltable material in the evaporation material of the optical functional layer is performed in a manner that an electron beam (EB) total energy (output power x time) is less than 1500 kJ.

[0014] [4] The plastic lens manufacturing method according to [3], characterized in that a thickness of the primer layer is 200 nm or more and less than 1000 nm.

[0015] [5] The plastic lens manufacturing method according to [3], characterized in that a thickness of the primer layer is 80 nm or more and less than 1000 nm, and a reflection electron trap is attached to an electron gun used after formation of the primer layer.

[0016] [6] The plastic lens manufacturing method according to [1], characterized in that the pre-melting before formation of the primer layer is performed in a state where the lens is disposed in an evaporation device.

[0017] [7] The plastic lens manufacturing method according to [6], characterized in that, before and after formation of the primer layer, pre-melting of a meltable material in the evaporation material of the optical functional layer is performed in a manner that an EB total energy (output power x time) is less than 1500 kJ, respectively.

[0018] [8] The method for manufacturing a plastic lens according to claim 7, wherein the primer layer has a thickness of 200 nm or more and less than 1000 nm, and a reflection electron trap is attached to an electron gun used before and after the primer layer is formed.

[0019] [9] The method for manufacturing a plastic lens according to claim 7, wherein the primer layer has a thickness of 80 nm or more and less than 1000 nm, and a reflection electron trap is attached to an electron gun used before and after the primer layer is formed.

[0020]

[10] The method for manufacturing a plastic lens according to any one of claims 1 to 9, wherein the optical functional layer is any one of an antireflection layer, a partial reflection layer, and a high reflection mirror.

[0021]

[11] The method for manufacturing a plastic lens according to claim 10, wherein in the formation of the optical functional layer, a step of bringing a surface temperature of the lens body to 60°C or higher is included.

[0022]

[12] The method for manufacturing a plastic lens according to claim 11, wherein the evaporation material that is pre-melted before the primer layer is formed is directly used for pre-melting after the primer layer is formed without being processed, and the evaporation process of the optical functional layer is performed after the pre-melting after the primer layer is completed.

[0023] According to the present application, it is possible to provide a method for manufacturing a plastic lens that is excellent in adhesion of an optical functional layer and productivity and further improved in durability. BRIEF DESCRIPTION OF DRAWINGS

[0024] Figure 1 is a schematic view of a cross section parallel to the optical axis Z and including the optical axis Z of a plastic lens that is one example (a plano-convex lens) formed by the manufacturing method of the present embodiment.

[0025] Figure 2 In (a) of FIG. 1, Figure 2 (a) of FIG. 1 is a schematic structural view (front view) of a representative evaporation apparatus having an evaporation source of a resistance heating type, Figure 2 (b) of FIG. 1 is a schematic structural view (front view) of a representative evaporation apparatus having an evaporation source of an electron beam heating type.

[0026] Figure 3 In (a) of FIG. 1, Figure 3 (a) of FIG. 1 is a flowchart showing a film formation step when pre-melting before the primer layer is formed is performed in a state where the substrate is not set in the evaporation apparatus in the manufacturing method of the present embodiment, Figure 3(b) is a flow chart showing a film forming step in which pre-melting before forming a primer layer is performed in a state where the substrate is set in a vapor deposition apparatus in the manufacturing method of this embodiment.

[0027] Figure 4 middle, Figure 4 (a) is an EB output-time graph of a procedure for pre-melting the fusible material in the vapor deposition material of the optical functional layer compiled so that the total EB energy (output power × time) becomes 340 kJ. Figure 4 (b) is the EB output-time curve of the program compiled in such a way that the total energy becomes 86 kJ. Figure 4 (c) is an EB output-time graph of a program compiled so that the total energy becomes 640 kJ.

[0028] The description of the accompanying drawings is as follows.

[0029] P: Plastic lens.

[0030] P1: Lens body.

[0031] P2: Primer.

[0032] P3: Optical functional layer.

[0033] Sa, Sb: noodles.

[0034] Z: optical axis.

[0035] 11: Evaporation device.

[0036] 12: Chamber.

[0037] 13: Resistance heating power supply.

[0038] 14: Evaporation cover.

[0039] 15: Boat.

[0040] 16: Shutter.

[0041] 17: Evaporation material.

[0042] 18: Substrate on which film is to be formed.

[0043] 19: Film.

[0044] 20: Evaporation device.

[0045] 21: Chamber.

[0046] 22: Electron gun.

[0047] 23: Electron gun power supply.

[0048] 24: Evaporation cover.

[0049] 25: Crucible

[0050] 26: Pole piece

[0051] 27: Shield

[0052] 28: Reflection electron trap

[0053] 29: Evaporation material

[0054] 30: Film formation target substrate

[0055] 31: Thin film

[0056] 32: Electron beam

[0057] 33: Reflection electron DETAILED DESCRIPTION

[0058] Hereinafter, a mode for carrying out the present application (hereinafter, referred to as "the present embodiment") will be explained in detail, but the present application is not limited to the following description, and can be carried out with various modifications within the scope of the gist thereof.

[0059] Note that, hereinafter, for the polymer of the thermoplastic acrylic resin contained in the plastic lens of the present embodiment, the structural unit constituting the polymer will be referred to as a "— monomer unit" and / or a "— structure unit" containing a plurality of the "— monomer unit".

[0060] In addition, for the constituting material of the "— monomer unit", it is sometimes omitted as "unit" and simply referred to as "— monomer".

[0061] < Plastic lens >

[0062] The plastic lens of the present embodiment can be any one of a biconvex lens, a plano-convex lens, a meniscus lens, a biconcave lens, a plano-concave lens, a plane lens, a cylindrical lens, a Fresnel lens, a lenticular lens, a fly-eye lens, a lens array, a micro-lens array, a prism lens, and the like.

[0063] Hereinafter, the manufacturing method of the plastic lens of the present embodiment will be explained with reference to the accompanying drawings.

[0064] Figure 1 is a schematic diagram of a cross section parallel to the optical axis Z and containing the optical axis Z, which is shown for one example (a plano-convex lens) of the plastic lens formed by the manufacturing method of the present embodiment.

[0065] The plastic lens P formed by the production method of the present embodiment at least has a lens body P1 made of resin, a primer layer P2 covering at least one face of the lens body (plastic lens substrate) P1, and an optical functional layer P3 covering the primer layer P2 from the side opposite to the lens body P1. That is, for the plastic lens P of the present embodiment, the primer layer P2 and the optical functional layer P3 are sequentially stacked on the lens body P1.

[0066] The plastic lens P formed by the production method of the present embodiment can have, in addition to the primer layer P2 and the optical functional layer P3, other layers such as an antifouling layer for making the surface of the plastic lens P difficult to be contaminated, a gas barrier layer for suppressing the penetration of water vapor into the plastic lens P.

[0067] Note that, in the present application, the lens body face refers to a surface or interface that exerts any optical action such as refraction or reflection on light rays or light beams incident on the face. In the present application, the lens body face is not limited to the surface of the lens body P1, but also includes the surface of the primer layer P2 and the surface of the optical functional layer P3. Figure 1 In the plastic lens P of the present embodiment, the faces of the lens body P1 are a face Sa and a face Sb, the face Sa is a non-spherical surface shape with a curvature radius R, and the face Sb is a planar shape (curvature radius: ∞). Figure 1 The plastic lens P of the present embodiment is an example in which only the face Sa is covered with the primer layer P2. In the plastic lens formed by the production method of the present embodiment, only one of the plurality of faces can be covered with the primer layer P2 and the optical functional layer P3, or two or more faces can be covered with the primer layer P2 and the optical functional layer P3. Figure 1 The plastic lens P of the present embodiment is an example in which only the face Sa is covered with the primer layer P2. In the plastic lens formed by the production method of the present embodiment, only one of the plurality of faces can be covered with the primer layer P2 and the optical functional layer P3, or two or more faces can be covered with the primer layer P2 and the optical functional layer P3.

[0068] In the production method of the plastic lens P, as described later, after the lens body P1 is molded, a primer layer forming step of forming the primer layer P2 and an optical functional layer forming step of forming the optical functional layer P3 are sequentially performed.

[0069] < Lens Body P1 >

[0070] The lens body P1 contains a thermoplastic acrylic resin. The "thermoplastic acrylic resin" refers to an acrylic resin having thermoplasticity, and it is preferable to further have heat resistance from the viewpoint of durability. Note that, "having heat resistance" means that the value of the Vicat softening temperature measured in accordance with ISO 306B50 is 110°C or higher, and "having low heat resistance" means that the Vicat softening temperature is less than 110°C.

[0071] The thermoplastic acrylic resin can be a single type or a combination of two or more types.

[0072] [Thermoplastic Acrylic Resin]

[0073] The glass transition temperature (Tg) of the thermoplastic acrylic resin contained in the lens body P1 is preferably 116°C or higher, more preferably 117°C or higher, and even more preferably 118°C or higher, as measured according to JIS-K7121, from the viewpoint of durability. In addition, the glass transition temperature Tg is preferably 200°C or lower, more preferably 180°C or lower, and even more preferably 160°C or lower, in consideration of the moldability and the like of the lens body P1.

[0074] The thermoplastic acrylic resin contained in the lens body P1 is a polymer containing an olefinically unsaturated monomer having at least one carboxyl group or carboxylate group as a monomer component. The thermoplastic acrylic resin can be a homopolymer of the olefinically unsaturated monomer or a copolymer of the olefinically unsaturated monomer and another monomer copolymerizable therewith. The proportion of the olefinically unsaturated monomer in the thermoplastic acrylic resin is preferably 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more, and is preferably 100% by mass or less, more preferably 95% by mass or less, and even more preferably 90% by mass or less, with respect to 100% by mass of the thermoplastic acrylic resin. If the proportion of the olefinically unsaturated monomer is within the above range, it is preferable from the viewpoints of heat resistance, low birefringence, moldability, and color tone.

[0075] The olefinically unsaturated monomer having a carboxyl group or a carboxylate group is not particularly limited, and examples thereof include methacrylic acid, acrylic acid, methacrylate, acrylate, and the like. As the ester bond-forming residue in the carboxylate group, examples include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, cyclopentyl, cyclohexyl, cyclooctyl, tricyclodecyl, isobornyl, phenyl, benzyl, 1-phenylethyl, 2-phenoxyethyl, 3-phenylpropyl, 2,4,6-tribromophenyl, and the like.

[0076] From the viewpoint of heat resistance, it is preferable that the thermoplastic acrylic resin contained in the lens body P1 have a ring structure in the structure. More specifically, it is preferable that the heat-resistant acrylic resin have a structural unit having a ring structure in the structure, and it is preferable that the structural unit having a ring structure include at least one of a cyclic imide-based structural unit, a lactone ring structural unit, an aromatic vinyl structural unit, and an alicyclic vinyl structural unit.

[0077] The structural unit having a ring structure can be a single one or a combination of two or more.

[0078] The proportion of the structural unit having a ring structure in the thermoplastic acrylic resin is preferably 15% by mass or more, more preferably 16% by mass or more, further preferably 17% by mass or more, and particularly preferably 18% by mass or more, based on 100% by mass of the thermoplastic acrylic resin. If the proportion of the ring structure is within the above range, it is preferable from the viewpoints of heat resistance, low birefringence, damage resistance, and moldability.

[0079] As the cyclic imide-based structural unit constituting the thermoplastic acrylic resin, maleimide-based structural units, glutarimide-based structural units, and the like can be given as examples.

[0080] (Maleimide-based structural unit)

[0081] As the maleimide-based structural unit constituting the thermoplastic acrylic resin, a structural unit represented by the following general formula (1) is preferable.

[0082] Chemical Formula 1

[0083]

[0084] In the general formula (1), R 1 represents any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, and an aryl group having 6 to 12 carbon atoms, and the alkyl group, the alkoxy group, the cycloalkyl group, and the aryl group can have a substituent on a carbon atom.

[0085] As the monomer used for forming the maleimide-based structural unit, there is no particular limitation, and maleimide; N-alkyl-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, and N-cyclohexylmaleimide; N-aryl-substituted maleimides such as N-phenylmaleimide, N-methylphenylmaleimide, N-ethylphenylmaleimide, N-butylphenylmaleimide, N-xylylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide can be given as examples.

[0086] Among the above monomers, from the viewpoint of imparting heat resistance and moisture resistance, N-cyclohexylmaleimide, N-phenylmaleimide, N-methylphenylmaleimide, N-(o-chlorophenyl)maleimide, N-(m-chlorophenyl)maleimide, and N-(p-chlorophenyl)maleimide can be given as preferable examples, from the viewpoint of ease of acquisition and imparting heat resistance, N-cyclohexylmaleimide and N-phenylmaleimide can be given as more preferable examples, and N-phenylmaleimide can be given as further preferable.

[0087] The above maleimide-based structural unit can be a single type or a combination of two or more types.

[0088] From the viewpoints of heat resistance, moldability, optical properties, and color tone stability, the content of the maleimide-based structural unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and further preferably 5 to 30% by mass, based on 100% by mass of the thermoplastic acrylic resin.

[0089] Note that in the present application, the content of the structural unit constituting the thermoplastic acrylic resin can be found by the method described in the Examples below.

[0090] (glutarimide-based structural unit)

[0091] The glutarimide-based structural unit constituting the thermoplastic acrylic resin can be formed after polymerization of the resin. As the glutarimide-based structural unit, a structural unit represented by the following general formula (2) is preferable.

[0092] Chemical Formula 2

[0093]

[0094] In the above general formula (2), R 1 and R 2 each independently represent a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, which can be substituted by a hydroxyl group, for example.

[0095] In addition, R 3 represents any one selected from the group consisting of a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, and a substituted or unsubstituted aryl group having 6 to 18 carbon atoms.

[0096] It is particularly preferable that R 1 , R 2 , and R 3 are each a methyl group.

[0097] The above glutarimide-based structural unit can be a single type or a combination of two or more types.

[0098] From the viewpoints of heat resistance, moldability, and optical properties, the content of the glutarimide-based structural unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and further preferably 5 to 30% by mass, based on 100% by mass of the thermoplastic acrylic resin.

[0099] The succinimide-based structural unit can be obtained by a method known per se, for example, a method in which a (meth)acrylate and / or a (meth)acrylic acid is copolymerized and then subjected to a urea or non-substituted urea reaction with ammonia or an amine under high temperature conditions, a method in which a methyl (meth)acrylate-styrene copolymer is reacted with ammonia or an amine, a method in which a poly(meth)acrylic anhydride is reacted with ammonia or an amine, and the like.

[0100] Specifically, there can be mentioned a method described in the specification of U.S. Patent No. 4246374 of R. M. Kopchik, and the like.

[0101] Further, the succinimide-based structural unit can also be formed by imidization of an acid anhydride such as maleic anhydride, a half ester of the acid anhydride with a linear or branched alcohol having 1 to 20 carbon atoms, and an α, β-ethylenically unsaturated carboxylic acid.

[0102] Further, as another preferred production method, there can be mentioned a method in which a (meth)acrylate and, as necessary, an aromatic vinyl monomer, another vinyl monomer are polymerized and then subjected to an imidization reaction to obtain a resin containing the above-described succinimide-based structural unit.

[0103] In the imidization reaction step, an imidization agent can be used, and a ring closure accelerator can be added as necessary. Here, as the imidization agent, ammonia or a primary amine can be used. As the primary amine, methylamine, ethylamine, n-propylamine, cyclohexylamine, and the like can be preferably used.

[0104] As the method for carrying out the imidization reaction, there is no particular limitation, and a method known per se can be used, for example, a method using an extruder, a transverse biaxial reaction device, or a batch-type reaction tank. As the extruder, there is no particular limitation, and a uniaxial extruder, a biaxial extruder, or a multiaxial extruder can be preferably used. More preferably, a tandem reaction extruder in which two biaxial extruders are arranged in series can be used.

[0105] Further, in the production of the above-described resin, in addition to the above-described imidization step, an esterification step in which a carboxyl group of the resin is treated with an esterification agent such as dimethyl carbonate can be included. At this time, a catalyst such as trimethylamine, triethylamine, tributylamine, and the like can also be used for the treatment.

[0106] The esterification step can be carried out, for example, by using an extruder or a batch-type reaction tank, similarly to the above-described imidization step.

[0107] Further, it is preferable to install a vent that can be depressurized to below atmospheric pressure in the device used, with the aim of removing excess esterification agent, a by-product or a monomer such as methanol.

[0108] (Lactone ring structural unit)

[0109] The lactone ring structure unit constituting the thermoplastic acrylic resin can be formed after polymerization of the resin. As the lactone ring structure unit, a structure unit represented by the following general formula (3) is preferable.

[0110] Chemical Formula 3

[0111]

[0112] In the general formula (3), R 1 , R 2 , and R 3 each independently represent a hydrogen atom or an organic group having 1 to 20 carbon atoms. Note that the organic group can also contain an oxygen atom.

[0113] The above lactone ring structure unit can be a single kind or a combination of two or more kinds.

[0114] From the viewpoint of heat resistance, moldability, and optical properties, the content of the lactone ring structure unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and further preferably 5 to 30% by mass, based on 100% by mass of the thermoplastic acrylic resin.

[0115] The method for forming the thermoplastic acrylic resin containing the lactone ring structure unit is not particularly limited, and a method in which a monomer having a hydroxyl group in a side chain (for example, a monomer (2-(hydroxymethyl) methyl acrylate or the like) represented by the structure of the following general formula (4)) is copolymerized with a monomer having an ester group such as a (meth) acrylate-based monomer, and the resulting copolymer is subjected to heat treatment in the presence / absence of a prescribed catalyst to introduce a lactone ring structure into the polymer can be mentioned.

[0116] Chemical Formula 4

[0117]

[0118] In the general formula (4), R 1 represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, which can be substituted with a hydroxyl group, for example.

[0119] R 2 represents a group having 1 to 12 carbon atoms, preferably a hydrocarbon group having 1 to 12 carbon atoms, which can be substituted with a hydroxyl group, for example.

[0120] It is particularly preferable that R 1 is a hydrogen atom and R 2 is a methyl group.

[0121] In addition, as long as the effect of the present application is exerted, a monomer of the structure represented by General Formula (4) can also remain in the thermoplastic acrylic resin in an unreacted form.

[0122] (aromatic vinyl structural unit)

[0123] As the aromatic vinyl structural unit constituting the thermoplastic acrylic resin, it is preferable to use a structural unit derived from an aromatic vinyl monomer represented by General Formula (5) below.

[0124] Chemical Formula 5

[0125]

[0126] In the General Formula (5), R 1 represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, which can be substituted by a hydroxyl group, for example.

[0127] R 2 is any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 8 carbon atoms, and an aryloxy group having 6 to 8 carbon atoms, R 2 may all be the same group or can be different groups. In addition, R 2 may also form a ring structure with each other.

[0128] n represents an integer of 0 to 5.

[0129] As the monomer used to form the aromatic vinyl structural unit, there is no particular limitation, and examples include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenylbenzene (a-methylstyrene), isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, isopropenyl octylbenzene, and the like.

[0130] Among the above, styrene and isopropenylbenzene are preferable, and styrene is more preferable in terms of imparting fluidity, improving the reduction of unreacted monomers, and the like.

[0131] In the thermoplastic acrylic resin of the present embodiment, they can be appropriately selected depending on the required properties.

[0132] The above aromatic vinyl structural unit can be a single type or a combination of two or more types.

[0133] From the viewpoint of heat resistance, moldability, and optical properties, the content of the aromatic vinyl structural unit is preferably 0 to 50% by mass, more preferably 2 to 40% by mass, and further preferably 4 to 30% by mass, based on 100% by mass of the thermoplastic acrylic resin.

[0134] (alicyclic vinyl structural unit)

[0135] The alicyclic vinyl structural unit constituting the thermoplastic acrylic resin can be formed after polymerization of the resin. As the alicyclic vinyl structural unit, a structural unit represented by the following general formula (6) is preferably used.

[0136] Chemical Formula 6

[0137]

[0138] In the general formula (6), R 1 ~R 3 independently represent any one of a hydrogen atom, a chain hydrocarbon group, a halogen atom, an alkoxy group, a hydroxyl group, an ether group, an ester group, a cyano group, an amide group, an imide group, a silyl group, and a chain hydrocarbon group substituted with a polar group (a halogen atom, an alkoxy group, a hydroxyl group, an ether group, an ester group, a cyano group, an amide group, an imide group, or a silyl group). Among them, a hydrogen atom or a chain hydrocarbon group having 1 to 6 carbon atoms is excellent in heat resistance and low water absorption, and is therefore preferred. As the halogen atom, a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom can be given. As the chain hydrocarbon group substituted with a polar group, for example, a haloalkyl group having 1 to 20, preferably 1 to 10, and more preferably 1 to 6 carbon atoms can be given. As the chain hydrocarbon group, for example, an alkyl group having 1 to 20, preferably 1 to 10, and more preferably 1 to 6 carbon atoms; an alkenyl group having 2 to 20, preferably 2 to 10, and more preferably 2 to 6 carbon atoms can be given.

[0139] X in the general formula (6) represents an alicyclic hydrocarbon group, and the number of carbon atoms constituting the alicyclic hydrocarbon group is usually 4 to 20, preferably 4 to 10, and more preferably 5 to 7. By setting the number of carbon atoms constituting the alicyclic structure to this range, birefringence can be reduced. In addition, the alicyclic structure is not limited to a monocyclic structure, and can be a polycyclic structure such as a norbornane ring, a dicyclohexane ring, or the like.

[0140] The alicyclic hydrocarbon group can have carbon-carbon unsaturation in an amount of 10% or less, preferably 5% or less, and more preferably 3% or less, of the total carbon-carbon bonds. By setting the carbon-carbon unsaturation of the alicyclic hydrocarbon group within this range, transparency and heat resistance are improved. In addition, any one of a hydrogen atom, a hydrocarbon group, a halogen atom, an alkoxy group, a hydroxyl group, an ether group, an ester group, a cyano group, an amide group, an imide group, a silyl group, and a chain hydrocarbon group substituted with a polar group (a halogen atom, an alkoxy group, a hydroxyl group, an ether group, an ester group, a cyano group, an amide group, an imide group, or a silyl group) can be bonded to the carbon constituting the alicyclic hydrocarbon group, with a hydrogen atom or a chain hydrocarbon group having 1 to 6 carbon atoms being preferred from the viewpoints of heat resistance and low water absorption.

[0141] In the structural unit represented by general formula (6), a structural unit represented by the following general formula (7) is preferred from the viewpoints of heat resistance and low water absorption.

[0142] Chemical Formula 7

[0143]

[0144] Ra, Rb, Rc, and Rd in general formula (7) each independently represent a hydrogen atom or a lower chain hydrocarbon group, with a hydrogen atom or a lower alkyl group having 1 to 6 carbon atoms being preferred from the viewpoints of heat resistance and low water absorption.

[0145] The above alicyclic vinyl structural unit can be a single type or a combination of two or more types.

[0146] The method for forming the thermoplastic acrylic resin containing the alicyclic vinyl structural unit is not particularly limited, and examples include (1) a method in which an aromatic vinyl compound is copolymerized with other monomers containing a (meth)acrylic acid or a (meth)acrylic acid ester, and the carbon-carbon unsaturation of the main chain and the aromatic ring is hydrogenated; (2) a method in which an alicyclic vinyl compound is copolymerized with other monomers containing a (meth)acrylic acid or a (meth)acrylic acid ester, and hydrogenation is performed as necessary, and the like. The method of (1) is preferred because it enables the alicyclic hydrocarbon copolymer to be obtained more efficiently.

[0147] The aromatic vinyl compound used in the method of the above (1) is not particularly limited, and examples include styrene, α-methylstyrene, α-ethylstyrene, α-propylstyrene, α-isopropylstyrene, α-tert-butylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-tert-butylstyrene, 5-tert-butyl-2-methylstyrene, monochlorostyrene, dichlorostyrene, monofluorostyrene, 4-phenylstyrene, and the like, with styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, and the like being preferred.

[0148] As the alicyclic vinyl compound used in the method of the above (2), there are no particular limitations, and examples include cyclobutyl ethylene, cyclopentyl ethylene, cyclohexyl ethylene (vinylcyclohexane), cycloheptyl ethylene, cyclooctyl ethylene, norbornyl ethylene, dicyclohexyl ethylene, a-methylcyclohexyl ethylene, a-tert-butylcyclohexyl ethylene, cyclopentenyl ethylene, cyclohexenyl ethylene, cycloheptenyl ethylene, cyclooctenyl ethylene, cyclodecenyl ethylene, norbornenyl ethylene, a-methylcyclohexenyl ethylene, and a-tert-butylcyclohexenyl ethylene, among which, cyclohexyl ethylene (vinylcyclohexane) is preferable.

[0149] From the viewpoint of heat resistance, molding processability, and optical properties, the content of the alicyclic vinyl structural unit is preferably 0 to 80% by mass, more preferably 2 to 60% by mass, and even more preferably 5 to 40% by mass, based on 100% by mass of the thermoplastic acrylic resin.

[0150] [Method for producing thermoplastic acrylic resin]

[0151] The method for producing the thermoplastic acrylic resin is not particularly limited as long as the above-described thermoplastic acrylic resin can be obtained, and a conventionally known method can be used. For example, the thermoplastic acrylic resin can be produced by using each monomer for forming each structural unit described above and using a bulk polymerization method, a solution polymerization method, a suspension polymerization method, a precipitation polymerization method, or an emulsion polymerization method. In the production of the thermoplastic acrylic resin, the bulk polymerization method or the solution polymerization method is preferably used, and the solution polymerization method is more preferably used.

[0152] In addition, the production of the thermoplastic acrylic resin can be continuous or batch.

[0153] In the method for producing the thermoplastic acrylic resin, it is preferable that the monomers are polymerized by radical polymerization.

[0154] In addition, in the method for producing the thermoplastic acrylic resin, a known polymerization initiator, a chain transfer agent, or the like can be used as necessary.

[0155] [Additives]

[0156] The lens body P1 is not particularly limited as long as the effects of the present application can be exerted, and various additives can be contained.

[0157] As the additive, there is no particular limitation, and for example, an antioxidant, a light stabilizer such as a hindered amine-based light stabilizer, an ultraviolet absorber, a release agent, a lubricant, another thermoplastic resin, a paraffin-based operation oil, a naphthenic-based operation oil, an aromatic-based operation oil, paraffin, an organic polysiloxane, a mineral oil, and the like can be exemplified as a softening agent / plasticizer, a flame retardant, an antistatic agent, an organic fiber, a pigment such as iron oxide, and an inorganic filler, a compatibilizer, a dispersant, a glass fiber, a carbon fiber, a metal whisker, a coloring agent, a phosphite, a phosphinite, a phosphate, another additive, or a mixture thereof, or the like.

[0158] The method of mixing the thermoplastic acrylic resin and the additive is not particularly limited, and for example, a method of mixing using a mixing machine such as an extruder, a heated roll, a kneader, a roll mixer, a Banbury mixer, or the like can be exemplified. Among them, from the viewpoint of productivity, mixing using an extruder is preferable. In order to reduce volatile components, it is preferable to provide an exhaust port in the extruder.

[0159] The mixing temperature can be set according to the preferred processing temperature of the thermoplastic acrylic resin and the other thermoplastic resin added as the additive, and is preferably 140 to 350°C, and more preferably 180 to 300°C.

[0160] From the viewpoints of ease of molding and mechanical strength, the weight average molecular weight (Mw) of the resin composition containing the thermoplastic acrylic resin and the optional additive is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and further preferably 70,000 to 200,000. When the weight average molecular weight (Mw) is within the above range, there is a tendency that the balance of the moldability, the mechanical strength of the lens body P1 becomes good.

[0161] In addition, from the viewpoints of ease of molding, mechanical strength, and solvent resistance, the molecular weight distribution (weight average molecular weight Mw / number average molecular weight Mn) of the resin composition containing the heat-resistant acrylic resin and the optional additive is preferably 1.25 to 3.00, more preferably 1.50 to 2.75, and further preferably 1.75 to 2.50. When the molecular weight distribution (Mw / Mn) is within the above range, there is a tendency that the balance of the moldability, the mechanical strength, and the solvent resistance of the lens body P1 becomes good.

[0162] Note that the weight average molecular weight (Mw) and the number average molecular weight (Mn) of the resin composition can be measured using gel permeation chromatography (GPC), and specifically, can be measured by the method described in the Examples described later.

[0163] The lens body P1 is formed by molding a resin composition containing a thermoplastic acrylic resin and optional additives. As the method of producing the lens body P1, molding methods such as injection molding, compression molding, injection compression molding, extrusion molding, cast molding, vacuum molding, pressure air molding, blow molding, injection molding, and the like can be used. In addition, the desired shape can also be obtained by cutting, turning, and grinding processing from a resin block. Among these, from the viewpoint of productivity, injection molding is preferred.

[0164] The injection molding method and the injection molding machine are not particularly limited, and conventionally known injection molding methods and injection molding machines can be used.

[0165] Generally, the injection molding method is composed of the following processes: (1) an injection process of melting the resin and filling the molten resin into the cavity of a mold whose temperature is controlled; (2) a holding pressure process of applying pressure to the cavity until the gate is sealed, and injecting the resin in an amount corresponding to the amount of the molten resin filled in the injection process that contacts the mold and shrinks due to cooling; (3) a cooling process of keeping the molded product until the resin is cooled after the holding pressure is released; and (4) a process of opening the mold and taking out the cooled molded product.

[0166] At this time, as the molding temperature, it is preferably in the range of Tg + 100°C to Tg + 180°C, and more preferably in the range of Tg + 110°C to Tg + 160°C, based on the glass transition temperature (Tg) of the resin composition. Here, the molding temperature refers to the barrel setting temperature of the injection molding machine. The higher the molding temperature, the better the shape transferability of the lens body P1 can be obtained, but coloring due to thermal degradation during residence in the molding machine is promoted under high temperature conditions, and thus the molding temperature should be appropriately selected.

[0167] In addition, as the mold temperature, it is preferably in the range of Tg - 70°C to Tg, and more preferably in the range of Tg - 50°C to Tg - 10°C, based on the glass transition temperature (Tg) of the resin composition.

[0168] In addition, as the injection speed, it can be appropriately selected depending on the thickness and size of the lens body P1 to be obtained, for example, it can be appropriately selected from the range of 2 to 1000 mm / sec.

[0169] In addition, as the pressure for holding pressure, it can be appropriately selected depending on the shape of the lens body P1 to be obtained, for example, it can be appropriately selected in the range of 30 to 150 MPa.

[0170] Here, the pressure for holding pressure refers to the pressure maintained by the screw for further feeding the molten resin from the gate after the molten resin is filled.

[0171] In addition, in order to relieve the residual stress generated by injection molding and reduce the phase difference of the lens body PI, an annealing process can also be performed. The temperature at the time of annealing is preferably in the range of Tg - 50°C to Tg, more preferably in the range of Tg - 30°C to Tg - 10°C, based on the glass transition temperature (Tg) of the resin composition.

[0172] <Undercoat Layer>

[0173] In the plastic lens P formed by the production method of the present embodiment, the undercoat layer P2 is a layer that covers at least one face of the lens body PI. The undercoat layer P2 improves the adhesion of the lens body (plastic lens substrate) PI to the optical functional layer P3, and suppresses the generation of cracks in the optical functional layer P3 under a high-temperature environment or a high-temperature high-humidity environment. Therefore, the plastic lens P formed by the production method of the present embodiment becomes a lens that is excellent in durability.

[0174] The undercoat layer P2 is composed of silicon oxide SiOx (1 < x < 2). As described later, for example, when film formation is performed using a vacuum evaporation method with SiO as the material, the composition of the undercoat layer P2 can be made to be silicon oxide SiOx (1 < x < 2) by performing film formation while oxidizing the evaporation material in an oxygen environment.

[0175] Generally, when a hygrothermal test is performed on a film formation product in which an optical functional layer composed of a metal oxide is formed on a resin substrate, cracks are generated in the optical functional layer due to the difference in the linear expansion coefficient and water absorption between the resin substrate and the optical functional layer, because the optical functional layer cannot follow the expansion of the resin substrate. However, the plastic lens P formed by the production method of the present embodiment has the undercoat layer P2 composed of silicon oxide SiOx (1 < x < 2) as a buffer layer between the lens body PI and the optical functional layer P3, and therefore, the generation of cracks is suppressed.

[0176] The refractive index of the undercoat layer P2 at a wavelength of 500 nm is preferably 1.44 or higher, more preferably 1.45 or higher, further preferably 1.46 or higher, and is preferably 1.64 or lower, more preferably 1.62 or lower, further preferably 1.60 or lower. When the refractive index is in this range, a high suppression effect on the generation of cracks after a hygrothermal test is exerted.

[0177] The above-mentioned refractive index of the undercoat layer P2 can be controlled by adjusting the composition of the silicon oxide SiOx (1 < x < 2), for example, when film formation of the undercoat layer P2 is performed by the vacuum evaporation method described later. If the oxygen partial pressure is increased (the amount of oxygen introduction is increased), the composition approaches SiO2 and the refractive index becomes low, and if the oxygen partial pressure is decreased (the amount of oxygen introduction is decreased), the composition approaches SiO and the refractive index becomes high.

[0178] Note that the refractive index of the undercoat layer P2 can be measured by the method described in the Examples described later.

[0179] The thickness (film thickness) of the primer layer P2 is preferably 80 nm or greater, more preferably 100 nm or greater, even more preferably 200 nm or greater, and preferably less than 1000 nm, more preferably 800 nm or less, and even more preferably 650 nm or less. When the thickness (film thickness) of the primer layer P2 is within this range, as described later, when the optical functional layer P3 is formed by an electron beam heating vacuum evaporation method, the reflected electrons can be prevented from reaching the surface of the lens body P1. This prevents embrittlement of the lens body P1 due to the reflected electrons and a decrease in adhesion between the lens body P1 and the optical functional layer P3 due to embrittlement of the lens body P1.

[0180] The thickness (film thickness) of the primer layer P2 can be determined, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or spectroscopic reflectance. Specifically, it can be determined by the method described in the examples below.

[0181] The primer layer P2 can be formed by a resistance heating vacuum deposition method. As described later, the resistance heating method prevents the generation of reflected electrons that may embrittle the lens body P1, thereby improving the adhesion between the lens body P1 and the primer layer P2.

[0182] In the vacuum evaporation method, a deposition material is heated in a vacuum chamber to vaporize or sublime it, and then adhered to the surface of a substrate located at a separate position in the chamber to form a thin film.

[0183] The evaporation device used in the vacuum evaporation method has a chamber and an evaporation source disposed in the chamber, and the substrate to be film-formed is held in the chamber. As the evaporation source, for example, a resistance heating type evaporation source or an electron beam heating type evaporation source is used. The schematic structure of a representative evaporation device is shown in FIG. Figure 2 . Figure 2 (a) is an example of a vapor deposition device having a resistance heating type vapor deposition source. Figure 2 (b) is an example of a vapor deposition device having an electron beam heating type vapor deposition source (electron gun). Although not shown, a vapor deposition device having both a resistance heating type vapor deposition source and an electron beam heating type vapor deposition source can also be used.

[0184] exist Figure 2In the evaporation device 11 of (a), 12 is a chamber, 13 is a resistance heating power source, 14 is an evaporation mask, 15 is a boat, and 16 is a shield. Note that the resistance heating power source 13 and the boat 15 are collectively referred to as an evaporation source. When the boat 15 is heated by the resistance heating power source 13, an evaporation material 17 is heated by the heat to generate vapor. The generated vapor reaches a substrate 18 to be formed on which is held in the evaporation mask 14 and is deposited, whereby a thin film 19 composed of the evaporation material 17 is formed. A plurality of boats 15 can be provided in the evaporation device 11, whereby the film thickness of the same evaporation material can be increased or a plurality of evaporation materials can be formed (not shown).

[0185] In addition, in Figure 2 In the evaporation device 20 of (b), 21 is a chamber, 22 is an electron gun, 23 is an electron gun power source, 24 is an evaporation mask, 25 is a crucible, 26 is a pole piece, and 27 is a shield. Note that the electron gun power source 23, the electron gun 22, and the crucible 25 are collectively referred to as an evaporation source. An electron beam 32 generated from the electron gun 22 is deflected by 150° or more (e.g., 180°, 270°) in a forward direction by a magnetic field formed by the pole piece 26 and is irradiated to an evaporation material 29 accommodated in the inside of the crucible 25. When the electron beam 32 is irradiated to the evaporation material 29, the evaporation material 29 is heated to generate vapor. The generated vapor reaches a substrate 30 to be formed on which is held in the evaporation mask 24 and is deposited, whereby a thin film 31 composed of the evaporation material 29 is formed. A plurality of crucibles 25 can be provided on a rotary stage, and by rotating the rotary stage, any of the crucibles can be arranged at a position where the electron beam is irradiated (not shown).

[0186] As described above, when the electron beam 32 is incident to the evaporation material 29, a part of the irradiated electrons is reflected (backscattered) from the surface of the evaporation material 29 due to the incident power and the material characteristics, and thus a certain amount of reflected electrons 33 is emitted. When the reflected electrons 33 reach the substrate 30 by repeatedly reflecting on the inner wall of the evaporation device or the like, resin decomposition (embrittlement of the substrate 30) occurs, which causes poor adhesion between the substrate 30 and the thin film 31 (the thin film 31 is easily peeled from the embrittled portion of the substrate 30). Acrylic resin is a material that is particularly susceptible to the influence of the reflected electrons 33 compared to other resins, and thus, in order to obtain good adhesion, it is necessary to suppress the influence of the reflected electrons 33. As a countermeasure, it is effective to make it difficult for the reflected electrons 33 to reach the substrate 30 and to reduce the amount of generation of the reflected electrons 33.

[0187] As a method of making it difficult for the reflected electrons 33 to reach the substrate 30, the film thickness of the primer layer P2 can be increased. Thus, even if a large amount of reflected electrons 33 heads toward the substrate 30, the primer layer P2 becomes a barrier layer and does not reach the surface of the acrylic resin (the interface with the primer layer P2), and the embrittlement of the substrate 30 can be suppressed.

[0188] On the other hand, as a method of reducing the amount of generation of the reflected electron 33, there are a method of reducing the energy of the electron beam 32 incident to the deposition material 29 and a method of capturing the reflected electron 33 so as not to be directed toward the substrate 30.

[0189] Since the energy of the electron beam 32 incident to the deposition material 29 is determined by the output power of the electron beam 32 and the irradiation (incident) time thereof, by reducing the output of the electron beam 32 and shortening the irradiation time in the film formation process, the amount of generation of the reflected electron 33 is reduced, and the embrittlement of the substrate 30 can be suppressed.

[0190] In addition, in order to capture the reflected electron 33 so as not to be directed toward the substrate 30, it is effective to attach a reflected electron trap in the electron gun 22. Thereby, the amount of the reflected electron 33 directed toward the substrate 30 is reduced, and the embrittlement of the substrate 30 can be suppressed.

[0191] Further, if the reflected electron trap is used, it is also possible to reduce the influence of the damage of the substrate, the change of the film quality of the thin film, and the like, which are accompanied by the temperature rise of the substrate when the reflected electron reaches the substrate, and thus is preferable. The reflected electron trap can use any reflected electron trap as long as it has a performance of sufficiently capturing the reflected electron, and as an example, there are a physical barrier type in which the reflected electron is collided multiple times by being provided inside an opening portion at a landing site of the reflected electron or inside a barrier such as an L-shaped / U-shaped barrier in a direction of advance of the reflected electron to attenuate the energy of the reflected electron, and a magnetic field deflection type in which the direction of advance of the reflected electron is deflected by a magnetic field to capture the reflected electron. In the case where the reflected electron trap is used, since the performance of capturing the reflected electron is high, it is preferable to use the magnetic field deflection type, and it is further preferable to use the magnetic field deflection type and the physical barrier type in combination. Figure 2 The reflected electron trap 28 of (b) is an example of the magnetic field deflection type.

[0192] As the steps of the general vacuum deposition of the primer layer P2 and the optical functional layer P3 of the optical film, the following six steps are provided.

[0193] (1) The substrate is fixed to the deposition mask, and the deposition mask is disposed above in the chamber. The chamber is vacuumed, and the chamber is brought to a high vacuum state.

[0194] (2) The substrate is heated together with the deposition mask using a halogen heater, a jacket heater, or the like. At this time, in order to uniformly heat, the deposition mask is rotated while being heated.

[0195] (3) In a state where the shield is closed, melting (premelting) of the evaporation material is performed. In the case of a sublimation material such as SiO2, since it can be sublimated in a particle state, pre-melting can not be performed strictly speaking, but from the viewpoint of making the transition to the step of (4) below smooth, it is preferable to perform preheating (hereinafter, melting and preheating will be collectively referred to as pre-melting). In the case of a dissolving material such as Ti3O5, pre-melting is necessary to prevent bumping (spattering) and stabilize the film formation rate. Note that in the case of electron beam heating, during pre-melting, reflected electrons sometimes also fly out from the gap of the shield, reach the substrate, and adversely affect adhesion, so it is preferable to perform it at low output / short time.

[0196] (4) After the pressure in the chamber reaches a prescribed vacuum pressure (base vacuum pressure) and the temperature of the substrate is stabilized, the shield is opened, and atoms / molecules of the evaporation material in a gas state are deposited on the surface of the substrate (evaporation).

[0197] (5) After a prescribed thickness of the evaporation film is formed on the substrate, the shield is closed, and the evaporation is ended.

[0198] (6) The vacuum is broken, and the evaporation mask and the substrate on which the evaporation film is formed are taken out from the chamber.

[0199] For the above six steps, steps (1), (2), (3) are usually performed at the same time, and then steps (4), (5), (6) are performed in order. However, as described later, it is also possible to perform step (3) first, then open the evaporation device again and set the substrate, and then perform steps (1), (2) in order or at the same time, and then perform steps (3) and thereafter. At this time, the evacuation in the chamber when step (3) is performed first is arbitrary. Note that in any order, the heating of the substrate in step (2) is arbitrary, and can not be performed.

[0200] In addition, in the case where a multilayer film is formed using different evaporation materials, steps (3) to (5) are repeated to perform film formation in the film formation of the second and subsequent materials (hereinafter, the film formation process of the evaporation material from the second material will be denoted as (3)', (4)', (5)'). At this time, the pre-melting of the evaporation material from the second material (step of (3)') can be performed at the same time as the pre-melting of the first material (step of (3)). By performing the step of (3)' at the same time as the step of (3), after the evaporation of the first material (step of (4)) is completed, it is possible to immediately transition to the evaporation of the second material (step of (4)'), and thus, it is possible to efficiently perform vacuum evaporation of a multilayer film composed of a plurality of materials.

[0201] In the step of (4), it is generally known to perform deposition while introducing oxygen into the chamber and reacting it with atoms / molecules of the deposition material to form an oxide film, or to use a plurality of deposition materials at the same time to form a mixture film. In addition, ion-assisted deposition (IAD) is widely used, in which the surface of a film being formed is irradiated with ions to impart effects such as increasing the packing density of the film and improving adhesion; ion plating, in which deposition particles that are gas are passed through plasma to impart positive charges to the deposition particles, and a negative charge is applied to the substrate to attract the gas deposition particles and deposit them to impart effects such as increasing the packing density of the film and improving adhesion, and the like.

[0202] In the film formation of the primer layer P2 of the present embodiment, in the evacuation of the chamber in the step of (1), it is preferable to perform the evacuation in such a manner that the pressure in the chamber becomes less than 2.0 x 10 -3 Pa.

[0203] In the heating of the deposition material in the steps of (3), (4), the method of resistance heating, electron beam heating, high-frequency induction heating, laser heating, or the like can be appropriately selected depending on the deposition material, the type of the substrate, and the target characteristics of the film being produced. In the film formation of the primer layer P2 of the present embodiment, SiO is used as the deposition material, and as the heating method, resistance heating type is required so as not to generate reflected electrons from the viewpoint of preventing embrittlement of the lens body PI.

[0204] In the deposition of the step of (4), the film can be formed while introducing oxygen into the chamber and reacting it with atoms / molecules of the deposition material. In the film formation of the primer layer P2 of the present embodiment, the amount of oxygen introduction (oxygen amount) is controlled so that the pressure in the chamber is less than 3.0 x 10 -2 Pa, preferably less than 2.8 x 10 -2 Pa, more preferably less than 2.6 x 10 -2 Pa, and preferably 1.0 x 10 - 2 Pa or more, more preferably 1.1 x 10 -2 Pa or more, further preferably 1.2 x 10 -2 Pa or more. If the pressure in the chamber is in this range, the primer layer P2 having the desired refractive index is formed, and high adhesion and a high inhibitory effect on the generation of cracks after a damp heat test are obtained.

[0205] <Optical Functional Layer>

[0206] In the plastic lens P formed by the manufacturing method of the present embodiment, the optical functional layer P3 is a layer that covers the primer layer P2 from the side opposite to the lens main body PI. That is, in the plastic lens P formed by the manufacturing method of the present embodiment, the primer layer P2 and the optical functional layer P3 are sequentially stacked on at least one surface of the lens main body PI.

[0207] As the optical functional layer P3, for example, an antireflection layer, a partial reflection layer, a high reflection mirror, an ultraviolet cut filter, an infrared cut filter, a band pass filter, a notch filter, an edge filter, a dichroic mirror, and the like can be given. In the present embodiment, any one of an antireflection layer, a partial reflection layer, and a high reflection mirror is formed, the antireflection layer has a function of preventing surface reflection in the plastic lens P, the partial reflection layer has a function of transmitting a part of incident light and reflecting a part thereof (an optical functional layer in which transmission and reflection are about 50% is particularly referred to as a half mirror layer), and the high reflection mirror has a function of reflecting almost all of the incident light. In the present embodiment, since the optical functional layer P3 is formed adjacent to the primer layer P2, it is preferable that the optical design of the optical functional layer P3 be performed in consideration of the optical properties and the thickness of the primer layer P2 to exhibit desired optical performance in the entire film structure in which the primer layer P2 and the optical functional layer P3 are combined.

[0208] It is preferable that the optical functional layer P3 be configured by combining a high refractive index film composed of a high refractive index material and a low refractive index film composed of a low refractive index material having a lower refractive index than the high refractive index material. In particular, it is preferable that the optical functional layer P3 be configured by a dielectric multilayer film in which the above-described high refractive index film and the above-described low refractive index film are alternately stacked. If the optical functional layer P3 is the dielectric multilayer film configured as described above, the reflectance can be more strictly adjusted with respect to light rays and light beams in a wide range of wavelength regions.

[0209] As the high refractive index material forming the high refractive index film, known materials can be used, and specifically, for example, titanium oxide, zirconium oxide, tantalum pentoxide, niobium pentoxide, zinc sulfide, cerium oxide, hafnium oxide, lanthanum titanate, antimony oxide, indium oxide, tin oxide, or the like can be used, and in addition thereto, a mixture thereof (Substance H series manufactured by Merck company, or the like) can be used. In addition, a material sold at a low oxidation number such as Ti2O3, Ti3O5, or a metal material can be used as the evaporation material, and evaporation can be performed while introducing oxygen into the chamber, and thus an oxide film into which an arbitrary amount of oxygen is introduced can also be formed. In the optical function layer P3 of the present embodiment, the high refractive index film is preferably composed of a high refractive index material including any one or more of titanium oxide and zirconium oxide. When the high refractive index film includes any one or more of titanium oxide and zirconium oxide, it is preferable from the viewpoints of adhesion to the lens main body PI and the primer layer P2, ease of material supply, film stability, and controllability of optical characteristics in the visible light region.

[0210] When the optical function layer P3 includes a plurality of high refractive index films, the composition of each high refractive index film can be appropriately set according to the design of the optical characteristics. Therefore, the composition of each high refractive index film can be the same or different.

[0211] The refractive index of each high refractive index film at a wavelength of 500 nm is preferably 1.80 or greater, more preferably 1.90 or greater, further preferably 2.00 or greater, preferably 2.50 or less, more preferably 2.45 or less, further preferably 2.40 or less.

[0212] Note that the refractive index of the high refractive index film can be measured by the method described in the Examples described later.

[0213] The thickness (film thickness) of each high refractive index film is preferably 5 nm or greater, more preferably 6 nm or greater, further preferably 7 nm or greater, preferably 150 nm or less, more preferably 140 nm or less, further preferably 130 nm or less. When the thickness (film thickness) of each high refractive index film is in this range, there is a tendency that the balance of film adhesion, damage resistance, and controllability of optical characteristics becomes good.

[0214] Note that the thickness (film thickness) of the high refractive index film can be found, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or spectroscopic reflectance, and specifically, can be found by the method described in the Examples described later.

[0215] As the low-refractive material forming the low-refractive film, known materials can be used, and specifically, for example, silicon oxide, magnesium fluoride, yttrium fluoride, Chiolite, halite, aluminum oxide, or the like can be used, and in addition thereto, a mixture thereof (Substance L series, Substance M series, or the like manufactured by Merck company) can be used. In addition, a material sold at a low oxidation number such as SiO, or a metal material can be used as the evaporation material, and evaporation can be performed while introducing oxygen into the chamber, and thus an oxidation film into which an arbitrary amount of oxygen is introduced can also be formed. In the optical functional layer P3 of the present embodiment, it is preferable that the low-refractive film contain silicon oxide (in which the refractive index at a wavelength of 500 nm is lower than that of the undercoat layer P2). When the low-refractive film contains the above-described silicon oxide, it is preferable from the viewpoints of easiness of material supply, controllability of oxidation degree, and stability of film formation. Note that, as a method of adjusting the refractive index of the low-refractive film containing silicon oxide to be lower than that of the undercoat layer P2, for example, a method of using SiO2 as the evaporation material of the silicon oxide in the optical functional layer P3, a method of adjusting the oxygen partial pressure (amount of oxygen introduction) when the undercoat layer P2 is formed as described above, and the like can be given. If the oxygen partial pressure is increased (the amount of oxygen introduction is increased), the composition approaches SiO2, and the refractive index becomes low, and if the oxygen partial pressure is decreased (the amount of oxygen introduction is decreased), the composition approaches SiO, and the refractive index becomes high.

[0216] When the optical functional layer P3 contains a plurality of low-refractive films, the composition of each low-refractive film can be appropriately set according to the design of the optical characteristics. Therefore, the composition of each low-refractive film can be the same or different.

[0217] The refractive index of each low-refractive film at a wavelength of 500 nm is preferably 1.10 or greater, more preferably 1.20 or greater, further preferably 1.30 or greater, preferably 1.70 or less, more preferably 1.60 or less, and further preferably 1.50 or less.

[0218] Note that the refractive index of the low-refractive film can be measured by the method described in the Examples described later.

[0219] The thickness (film thickness) of each low-refractive film is preferably 2 nm or greater, more preferably 3 nm or greater, and further preferably 4 nm or greater, and is preferably 200 nm or less, more preferably 190 nm or less, and further preferably 180 nm or less. When the thickness (film thickness) of each low-refractive film is in this range, there is a tendency that the balance of the control of the film adhesion, the damage resistance, and the optical characteristics becomes good.

[0220] Note that the thickness (film thickness) of the low-refractive-index film can be found, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or spectroscopic reflectance, and specifically, by the method described in the Examples below.

[0221] The total thickness (total film thickness) of the optical functional layer P3 is preferably 100 nm or greater, more preferably 150 nm or greater, further preferably 200 nm or greater, preferably 600 nm or less, more preferably 500 nm or less, and further preferably 400 nm or less. When the total thickness (total film thickness) of the optical functional layer P3 is within this range, there is a tendency for the adhesion of the optical functional layer P3 to the lens body PI and the primer layer P2 to be improved.

[0222] Note that the total thickness (total film thickness) of the optical functional layer P3 can be found, for example, by direct observation of a cross section using an electron microscope, ellipsometry, or spectroscopic reflectance, and specifically, by the method described in the Examples below.

[0223] The optical functional layer P3 of the present embodiment is formed by a vacuum evaporation method, like the primer layer P2, and is formed by a vacuum evaporation method of the electron beam heating type as the heating method for the evaporation material. In general, dry film formation methods such as vacuum evaporation methods are superior in shape control compared to wet film formation methods, and thus, for the plastic lens P formed by the production method of the present embodiment, the primer layer P2 and the optical functional layer P3 are formed by a vacuum evaporation method, and thus, a plastic lens with excellent shape precision that can also be used for applications requiring highly controlled surface shapes is obtained. In addition, for the plastic lens P of the present embodiment, since the film formation of the primer layer P2 and the optical functional layer P3 can be performed continuously by a vacuum evaporation method, the number of steps and the operation time can be reduced, and the productivity is excellent.

[0224] In the film formation of the optical functional layer P3 of the present embodiment, an electron beam type is used as the heating method in the heating of the evaporation material in steps (3) and (4) of the vacuum evaporation described above, from the viewpoint of work efficiency and the degree of freedom in material selection. At this time, the temperature inside the chamber and the temperature of the lens body increase due to radiation heat and the like from the evaporation material, and from the viewpoint of adhesion, the surface temperature of the lens body is preferably 60°C or greater.

[0225] In the production method of the present embodiment, the pre-melting of the evaporation material of the optical functional layer P3 of step (3) is performed before and after the formation of the primer layer P2. The evaporation material pre-melted before the formation of the primer layer P2 is used as it is for the pre-melting after the formation of the primer layer P2. Although the pre-melting is performed with the shutter closed, reflected electrons flying out from the gap of the shutter reach the substrate and adversely affect the adhesion, and therefore measures such as reducing the amount of generation of reflected electrons are required. In the production method of the present embodiment, the pre-melting of the evaporation material of the optical functional layer P3 is performed before the formation of the primer layer P2, and the surface of the evaporation material is flat except for being closely packed in the crucible, and therefore the total energy (output power x time) of the EB required for heating the evaporation material can be reduced in the pre-melting after the formation of the primer layer P2, and in addition to the suppression of the generation and scattering of reflected electrons, the bumping of the evaporation material can also be suppressed. However, since the pre-melting of the evaporation material of the optical functional layer P3 is performed at a stage where the primer layer P2 has not been formed, the substrate is directly affected by reflected electrons when the substrate is set in the evaporation apparatus at that time, and therefore the contents of the countermeasures against reflected electrons differ greatly depending on the setting condition of the substrate.

[0226] In Figure 3 In the case of the film formation procedure of (a), i.e., in the case where the pre-melting of the evaporation material of the optical functional layer P3 is performed before the formation of the primer layer P2 with the substrate not set in the evaporation apparatus, the reflected electrons have no effect on the substrate at that time, and therefore no countermeasures are required. However, after the substrate is set in the evaporation apparatus and the primer layer P2 is formed, the pre-melting of the evaporation material of the optical functional layer P3 is performed again, but if the total energy (output power x time) at that time is too large, a large amount of reflected electrons are generated, the primer layer does not function as a barrier layer and the substrate is embrittled, and therefore it is important to reduce the total energy of the EB at the time of pre-melting. Specifically, the total energy of the EB at the time of pre-melting of the fusible material in the evaporation material of the optical functional layer is less than 1500 kJ, and from the viewpoint of productivity, it is preferably less than 1250 kJ, and further preferably less than 1000 kJ. Note that, Figure 4(a), (b), and (c) are examples of programs compiled in such a way that the total energy of the pre-melting is 340kJ, 86kJ, and 640kJ, respectively. In addition, the sublimable material in the vapor deposition material of the optical functional layer can be sublimated in a granular state. Therefore, strictly speaking, pre-melting can also be omitted. However, in the case of implementation, in order to reduce reflected electrons and improve productivity, it is preferably carried out with low energy. Furthermore, even if the above-mentioned countermeasures are implemented, the embrittlement of the substrate caused by reflected electrons cannot be suppressed when the film thickness of the primer layer P2 is small, and peeling is likely to occur. Therefore, it is preferred that when the film thickness of the primer layer P2 is less than 200nm (for example, preferably 80nm or more, more preferably 100nm or more), a reflected electron trap is provided in the electron gun used to reduce the number of reflected electrons generated and reaching the substrate during pre-melting. When the film thickness of the primer layer P2 is more than 200nm, even if the number of reflected electrons is not reduced, the primer layer P2 can suppress the reflected electrons from reaching the substrate. Therefore, it is not necessary to provide a reflected electron trap in the electron gun used, but there is no problem with it.

[0227] On the other hand, Figure 3 In the case of the film forming process (b), that is, before forming the primer layer P2, when pre-melting of the vapor deposition material of the optical functional layer P3 is carried out in a state where the substrate is set in the vapor deposition device, the influence of the reflected electrons received by the substrate is extremely large, and therefore, a reflected electron trap must be provided. However, the reflected electron trap is not a device that can capture all reflected electrons, and in this pre-melting process, the primer layer (the barrier layer for reflected electrons) P2 is not formed. Therefore, if the total EB energy (output power × time) at this time is too large, the reflected electrons cause embrittlement of the substrate. Therefore, it is also important to reduce the total EB energy during pre-melting. Specifically, the total EB energy during pre-melting of the fusible material in the vapor deposition material of the optical functional layer is set to less than 1500kJ. From the viewpoint of productivity, it is preferably less than 1250kJ, and more preferably less than 1000kJ. It should be noted that, Figure 4 (a), (b), and (c) are examples of programs compiled so that the total energy of the pre-melting is 340 kJ, 86 kJ, and 640 kJ, respectively. Furthermore, since the sublimable material in the vapor deposition material of the optical functional layer can sublime in a granular state, strictly speaking, pre-melting is not necessary. However, if pre-melting is performed, it is preferably performed at a low energy level to reduce reflected electrons and improve productivity.

[0228] Then, after the formation of the undercoat layer P2, pre-melting of the evaporation material of the optical functional layer P3 is performed, but if the EB total energy (output power x time) at this time is too large, a large amount of reflected electrons are generated, the undercoat layer does not function as a barrier layer and the substrate is embrittled. Therefore, it is also important to reduce the EB total energy at the time of pre-melting after the formation of the undercoat layer P2. Specifically, the EB total energy at the time of pre-melting of the meltable material among the evaporation materials of the optical functional layer is set to less than 1500 kJ, and from the viewpoint of productivity, it is preferably less than 1250 kJ, and further preferably less than 1000 kJ. Note that, Figure 4 (a), (b), (c) of (a), (b), (c) are one example of a program prepared so that the total energy of the pre-melting is 340 kJ, 86 kJ, 640 kJ, respectively. In addition, the sublimable material among the evaporation materials of the optical functional layer can be sublimated in a granular state, and therefore, pre-melting can not be performed strictly speaking, but in the case of performing it, it is preferable to perform it with a small amount of energy in order to reduce reflected electrons and improve productivity. Further, even if the above countermeasures are performed, in the case where the film thickness of the undercoat layer P2 is small, the embrittlement of the substrate due to reflected electrons cannot be suppressed, and peeling is likely to occur, and therefore, when the film thickness of the undercoat layer P2 is less than 200 nm, it is necessary to continue to attach a reflected electron trap to the electron gun used, and to reduce the number of reflected electrons generated at the time of pre-melting and reaching the substrate. In the case where the film thickness of the undercoat layer P2 is 200 nm or more, even if the number of reflected electrons is not reduced, the undercoat layer P2 can suppress the reflected electrons from reaching the substrate, and therefore, it is not necessary to continue to attach a reflected electron trap to the electron gun used, but it is not problematic to attach it.

[0229] Note that the amount of generation of reflected electrons is not determined by the amount of use of the evaporation material, but by the size of the EB energy. Therefore, the upper limit value (1500 kJ) of the EB total energy at the time of the above pre-melting is an absolute value that is independent of the amount of use of the evaporation material, the number of crucibles, and the size. In the case where less than 1500 kJ is satisfied, in the pre-melting of the evaporation material in steps (3), (3)', it is possible to perform pre-melting on a plurality of crucibles containing the evaporation material of the optical functional layer P3 before step (4).

[0230] There is no particular limitation on the shape of the evaporation material, and the evaporation material (SiO) of the undercoat layer P2 and the evaporation material of the optical functional layer P3 can be appropriately selected in consideration of the specifications / characteristics of the evaporation apparatus, the availability of the evaporation material, and the like. Specifically, pellet shape, tablet shape, granular shape, powder shape, fan shape, ring shape, rod shape, and the like can be given.

[0231] In addition, in the evaporation in step (4), it is preferable to control the amount of oxygen introduction so that the pressure in the chamber is 1.0 x 10 -3 Pa to 5.0 x 10 -2The range of Pa. At this time, the aforementioned ion-assisted evaporation method can also be used, but it is necessary to adjust the amount of introduced gas to the above-mentioned pressure range in consideration of the pressure rise caused by oxygen, argon or a mixed gas thereof that is suitable as the introduced gas. It should be noted that, since a dense film is obtained by applying ion assistance, there is an effect of suppressing the optical shift caused by the adsorption of water, and the effect of efficiently implementing the oxidation of oxygen-deficient compounds when the amount of oxygen introduced is large. However, if the refractive index changes and deviates from the desired optical properties or the amount of gas introduced is too much, there is a problem that the film density becomes higher, thereby increasing the film stress and easily causing deformation of the substrate, cracking and peeling of the film, or the mean free path of the vaporized vaporized particles is shortened, thereby causing a decrease in the film forming rate, or an increase in the energy that should be applied to the vapor deposition material in order to obtain a specified film thickness. When using the ion-assisted evaporation method, it is preferred to consider the above-mentioned advantages / disadvantages and appropriately set / design the type of introduced gas, the introduction amount, the auxiliary conditions, the film structure, etc.

[0232] Items using plastic lenses

[0233] The plastic lens of this embodiment can be suitably used as lenses in household appliances, OA equipment, AV equipment, battery and electrical equipment parts, lighting equipment, automobile parts, and the like.

[0234] One preferred example of its use is in lenses for VR (Virtual Reality) head-mounted displays (HMDs). Head-mounted displays are image display devices worn on the head, and therefore require compactness, lightness, and minimal discomfort. One method for miniaturization has been proposed, combining a quarter-wave plate and a reflective polarizer with a lens. This method changes the polarization state of light passing through the lens, switching between reflection and transmission, allowing the image to travel one and a half round trips within a single lens (see, for example, U.S. Patent No. 6,563,638 and Japanese Patent Application Laid-Open No. 2017-21321).

[0235] The above method is based on the following principles, for example.

[0236] A 1 / 4 wavelength plate and a reflective polarizing plate are arranged on the back surface of a lens on which a partial reflection coating is applied to the front surface. Light that is incident on the front surface of the lens as circularly polarized light is converted into linearly polarized light by the 1 / 4 wavelength plate after passing through the lens. The linearly polarized light is reflected by the reflective polarizing plate and is converted into circularly polarized light that is opposite to the original by the 1 / 4 wavelength plate, is incident on the lens from the back surface, and reaches the partial reflection coating portion of the front surface. Light that is emitted from the back surface after being reflected by the partial reflection coating portion becomes linearly polarized light that is 90° different from the original direction by the 1 / 4 wavelength plate and passes through the reflective polarizing plate, and is incident on the eye as an image. In this manner, even in a thin optical module, a high magnification and a wide field of view can be obtained.

[0237] If the polarization state changes during passing through the lens, for example, a portion of light passes through the reflective polarizing plate after passing through the lens for the first time, and an image with a low magnification and an image with a high magnification overlap, and thus it is difficult to obtain a clear image, and thus a lens with a low birefringence is required. In addition, a change in the shape of the lens due to a change in humidity during use is not suitable for imaging properties, and thus a lens with a low moisture absorption and a high shape stability in a high temperature and high humidity environment is required. In this regard, the plastic lens formed by the production method of the present embodiment is excellent in shape accuracy and has extremely good durability, and thus is preferable.

[0238] In addition, as other examples in which the plastic lens formed by the production method of the present embodiment is preferably used, as a lens in a household product, an OA device, an AV device, a component for a battery electrical device, an illumination device, and the like, for example, a lens for a camera of a smartphone, a camera for a tablet, a lens used in a telescopic camera (periscope camera) of a folded optics, a lens used in a VR (Virtual Reality) / AR (Augmented Reality) / MR (Mixed Reality) / SR (Substitutional Reality) / DR (Diminished Reality) / XR (Cross Reality) head-mounted display, a liquid crystal projector, a near-infrared sensor (LiDAR; Light Detection and Ranging), and the like, particularly, an optical lens of a small size, a thin wall, and a non-uniform shape, a lens for optical communication, a lens, a Fresnel lens, a phase plate provided with a micro lens array, and the like can be given.

[0239] As a lens in a component for a car and the like, a lens used in a head-up display, a camera lens for a car (particularly, a front lens), and the like can be given.

[0240] In addition, as the lens used in the floating display, for example, a base material of a retroreflective sheet or a partially transmissive lens can be given; a microlens array used for constituting an array of a dihedral angle reflector; a lens used for enlarging, reducing, or correcting an image surface or aberration; and the like can be given.

[0241] Examples

[0242] Hereinafter, the content of the present application will be specifically described by giving examples and comparative examples. Note that the present application is not limited to the following examples.

[0243] The measurement and evaluation method of the thermoplastic acrylic resin produced in the production examples are as follows.

[0244] [Analysis of Structural Units]

[0245] Unless otherwise specified, the measurement was performed by 1 H-NMR measurement and 13 The structural units of the thermoplastic acrylic resin produced in the production examples were identified by C-NMR measurement, and the amount of existence was calculated. 1 H-NMR measurement and 13 The measurement conditions of the C-NMR measurement are as follows.

[0246] Measurement apparatus: ECZ400 manufactured by JEOL Ltd.

[0247] Measurement solvent: CDCl3 (deuterated chloroform) or DMSO-d6 (deuterated dimethyl sulfoxide).

[0248] Measurement temperature: 40°C.

[0249] [Measurement of Molecular Weight]

[0250] The weight average molecular weight (Mw) and the number average molecular weight (Mn) of the thermoplastic acrylic resin produced in the production examples were measured under the following apparatus and conditions.

[0251] Measurement apparatus: HLC-8320 GPC manufactured by TOSOH CORPORATION.

[0252] The measurement conditions are as follows.

[0253] Chromatography column: One TSK guard column Super H-H, two TSKgel Super HM-M, and one TSKgel Super H2500 were connected in series and used.

[0254] Chromatography column temperature: 40°C.

[0255] Elution solvent: tetrahydrofuran, flow rate: 0.6 mL / min, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added as an internal standard.

[0256] Detector: RI (differential refractive) detector.

[0257] Detection sensitivity: 3.0 mV / min.

[0258] Sample: 0.02 g of tetrahydrofuran 20 mL solution of the thermoplastic acrylic resin.

[0259] Injection amount: 10 μL.

[0260] Standard curve standard sample: The following 10 kinds of polymethyl methacrylate (manufactured by Polymer Laboratories; PMMA calibration kit M-M-10) having different molecular weights with known weight peak molecular weight were used.

[0261] Weight peak molecular weight (Mp) Standard reagent 1 1916000 Standard reagent 2 625500 Standard reagent 3 298900 Standard reagent 4 138600 Standard reagent 5 60150 Standard reagent 6 27600 Standard reagent 7 10290 Standard reagent 8 5000 Standard reagent 9 2810 Standard reagent 10 850

[0262] Under the above conditions, the RI detection intensity was measured with respect to the elution time of the thermoplastic acrylic resin.

[0263] Based on the standard curve obtained by the measurement of the above standard curve standard sample, the weight average molecular weight (Mw) and the number average molecular weight (Mn) of the thermoplastic acrylic resin were calculated, and the molecular weight distribution (Mw / Mn) was determined using the values.

[0264] [Measurement of glass transition temperature]

[0265] The glass transition temperature (Tg) (°C) of the thermoplastic acrylic resin was measured according to JIS-K7121.

[0266] First, the state of the sample was adjusted (left at 23°C for 1 week) under standard conditions (23°C, 50% RH), and about 10 mg was cut out from the sample at four points (four places) as test pieces.

[0267] Then, using a differential scanning calorimeter (manufactured by Perkin Elmer Japan, Diamond DSC) under a nitrogen flow of 25 mL / min, a DSC curve was plotted during a second temperature increase under the above temperature increase conditions, and the intersection (midpoint glass transition temperature) of the stepwise change portion curve of the second temperature increase and the straight line equal in distance to the respective baseline extensions in the vertical axis direction was measured as the glass transition temperature (Tg) (°C). Four points were measured for each sample, and the arithmetic mean (rounded off to one decimal place) of the four points was taken as the measured value.

[0268] [Measurement of Vicat Softening Temperature]

[0269] A thermoplastic acrylic resin was charged into an injection molding machine (manufactured by Shibaura Machine Co., Ltd., EC-100SX), and a 1A dumbbell-shaped test piece was molded in accordance with ISO 8257-2. After the test piece was conditioned in an oven at a prescribed temperature for 16 hours, it was cooled in a desiccator at 23°C for 1 hour, and the Vicat softening temperature (°C) of the thermoplastic acrylic resin was measured in accordance with ISO 306 B50.

[0270] The raw materials used in the production examples were as follows.

[0271] [Monomers]

[0272] Methyl methacrylate (MMA): manufactured by Asahi Kasei Corporation.

[0273] N-phenylmaleimide (phMI): manufactured by Japan Catalyst Co., Ltd.

[0274] N-cyclohexylmaleimide (chMI): manufactured by Japan Catalyst Co., Ltd.

[0275] 2-(hydroxymethyl) methyl acrylate (RHMA): manufactured by Combi-Blocks company.

[0276] Styrene (St): manufactured by FUJIFILM Wako Pure Chemical Corporation.

[0277] [Organic Solvents]

[0278] M-xylene (mXy): manufactured by Mitsubishi Gas Chemical Company, Inc.

[0279] Toluene: manufactured by FUJIFILM Wako Pure Chemical Corporation

[0280] Methyl isobutyrate: manufactured by Kanto Chemical Co., Inc.

[0281] [Polymerization initiator]

[0282] 1,1-di(tert-butylperoxy)cyclohexane: manufactured by NOF Corporation, Perhexa C

[0283] Tert-amyl peroxy isononanoate: manufactured by Arkema Yoshitomi, Ltd., Luperox 570

[0284] Tert-amyl peroxy 2-ethylhexanoate: manufactured by Arkema Yoshitomi, Ltd., Luperox 575

[0285] [Chain transfer agent]

[0286] n-Octyl mercaptan: manufactured by Chevron Phillips Chemical International Ltd.

[0287] [Other additives, etc.]

[0288] Stearyl phosphate: manufactured by Sakai Chemical Industry Co., Ltd., Phoslex A-18

[0289] Monomethylamine: manufactured by Mitsubishi Gas Chemical Co., Inc.

[0290] Dimethyl carbonate: manufactured by FUJIFILM Wako Pure Chemical Corporation

[0291] Triethylamine: manufactured by FUJIFILM Wako Pure Chemical Corporation

[0292] Pd / C: manufactured by N.E. CHEMCAT CORPORATION

[0293] Rikemal H-100: manufactured by Riken Vitamin Co., Ltd.

[0294] (Production Example 1: Thermoplastic acrylic resin A)

[0295] MMA 358.6 kg, N-phenylmaleimide (hereinafter, referred to as phMI) 29.4 kg, N-cyclohexylmaleimide (hereinafter, referred to as chMI) 67.7 kg, n-octyl mercaptan 0.77 kg as a chain transfer agent, m-xylene (hereinafter, referred to as mXy) 224.3 kg were measured and added to a 1.25 m 3 The reactor was stirred to obtain a mixed monomer solution.

[0296] Then, MMA 88.0 kg, phMI 6.3 kg, mXy 142.4 kg were measured and added to the tank 1, and stirred to obtain a replenishing mixed monomer solution.

[0297] The inside liquid of the reactor was subjected to nitrogen bubbling at a rate of 30 L / min for 1 hour, and the tank 1 was subjected to nitrogen bubbling at a rate of 10 L / min for 30 minutes to remove dissolved oxygen.

[0298] Then, the temperature of the solution in the reactor was raised to 115°C by blowing steam into the jacket, and a polymerization initiator solution in which 1,1-di(tert-butylperoxy)cyclohexane 0.470 kg was dissolved in mXy 1.905 kg was added at a rate of 1.0 kg / hour while stirring at 50 rpm to start the polymerization.

[0299] Note that the temperature of the solution in the reactor was controlled to 115 ± 2°C by temperature adjustment using the jacket during the polymerization. The rate of addition of the initiator solution was reduced to 0.5 kg / hour 30 minutes after the start of the polymerization.

[0300] In addition, the entire replenishing mixed monomer solution was added at a constant rate from the tank 1 over 4 hours after the start of the polymerization.

[0301] Further, the rate of addition of the initiator solution was reduced to 0.25 kg / hour 3.5 hours after the start of the polymerization, and the addition was stopped 5 hours after the start of the polymerization.

[0302] The polymerization was ended 12 hours after the start of the polymerization to obtain a polymer solution of a thermoplastic acrylic resin having a cyclic structure in the structure (main chain).

[0303] The polymer solution was supplied to a concentration device composed of a tubular heat exchanger and a gasification tank preheated to 250°C to be devolatilized. The vacuum degree of the gasification tank was 10 to 15 Torr. The resin flowing from the gasification tank was discharged with a gear pump, extruded from a die, and pelletized after water cooling to obtain a thermoplastic acrylic resin A.

[0304] The composition of the obtained particles was confirmed, and as a result, the structural units from each of the monomers of MMA, phMI, chMI in the copolymer were 81.0 mass%, 6.6 mass%, and 12.4 mass%, respectively. In addition, the weight average molecular weight was 108,000, Mw / Mn was 2.04, the glass transition temperature was 134°C, and the Vicat softening temperature was 124°C.

[0305] (Production Example 2: Thermoplastic acrylic resin B)

[0306] As the resin of the raw material, a methyl methacrylate-styrene copolymer (styrene content: 8 mass%) having a molecular weight of 100,000 was used, and as the imidization agent, monomethylamine was used, and a 15-mm-diameter intermeshing co-rotating twin-screw extruder was used to produce a glutarimide resin. The set temperature of each temperature adjustment zone was set to 230 to 250°C, and the screw rotation number was set to 150 rpm. The methyl methacrylate-styrene copolymer (hereinafter, also referred to as "MS resin") was supplied at 2 kg / hour, the resin was melted and filled by the kneading block, and then monomethylamine at 8 parts by mass with respect to the resin was injected from the nozzle. A reverse screw was inserted at the end of the reaction zone, and the resin was filled. The pressure of the exhaust port was reduced to -0.092 MPa to remove the by-products after the reaction and excess monomethylamine. The resin coming out in strands from the die provided at the outlet of the extruder was cooled with a water tank, and then pelletized with a pelletizer, thereby obtaining a glutarimide MS resin intermediate (1).

[0307] Then, for a 15-mm-diameter intermeshing co-rotating twin-screw extruder, the set temperature of each temperature adjustment zone of the extruder was set to 230°C, and the screw rotation number was set to 150 rpm. The obtained glutarimide MS resin intermediate (1) was supplied at 1 kg / hour from the hopper, the resin was melted and filled by the kneading block, and then a mixed solution of dimethyl carbonate at 0.8 parts by mass and triethylamine at 0.2 parts by mass with respect to the resin was injected from the nozzle to reduce the carboxyl group in the resin. A reverse screw was inserted at the end of the reaction zone, and the resin was filled. The pressure of the exhaust port was reduced to -0.092 MPa to remove the by-products after the reaction and excess dimethyl carbonate. The resin coming out in strands from the die provided at the outlet of the extruder was cooled with a water tank, and then pelletized with a pelletizer, thereby obtaining a glutarimide MS resin intermediate (2).

[0308] Further, the glutarimide-converted MS resin intermediate (2) was fed into an intermeshing co-rotating twin-screw extruder having a 15 mm diameter, under conditions where the set temperature at each temperature adjustment zone of the extruder was 230°C, the screw rotation number was 150 rpm, and the supply amount was 1 kg / hour. The pressure at the exhaust port was reduced to -0.095 MPa to remove the unreacted raw materials and the like, which were volatile. The devolatilized imide resin, which was discharged from a die provided at the outlet of the extruder as a strand, was cooled with a water tank, and then pelletized with a pelletizer, thereby obtaining a thermoplastic acrylic resin B (glutarimide-converted MS resin).

[0309] The weight average molecular weight of the thermoplastic acrylic resin B was 8.5 x 105, Mw / Mn was 1.8, the content of monomer units in the copolymer was 8 mass% for styrene units, 82 mass% for MMA units, and 10 mass% for glutarimide units, the glass transition temperature was 128°C, and the Vicat softening temperature was 120°C.

[0310] (Production Example 3: Thermoplastic Acrylic Resin C)

[0311] Methyl 2-(hydroxymethyl)acrylate (hereinafter, abbreviated as RHMA) 5.40 parts by mass, methyl methacrylate (hereinafter, abbreviated as MAA) 37.6 parts by mass, styrene (hereinafter, abbreviated as St) 0.450 parts by mass, and toluene 90.0 parts by mass were fed into a reaction vessel equipped with a stirring device, a temperature sensor, a cooling tube, a nitrogen introduction tube, and a dropping pump, while nitrogen was introduced, and the temperature was raised to 105°C.

[0312] As the initial initiator, solution polymerization was performed at 105°C to 110°C while dropping a solution composed of 3.63 parts by mass of toluene and 0.245 parts by mass of t-amyl peroxyisononanoate over 9 minutes. Then, 11 minutes later, a solution composed of 4.42 parts by mass of toluene and 0.298 parts by mass of t-amyl peroxyisononanoate as the dropping initiator was dropped over 180 minutes. In addition, at the same time as the dropping of the dropping initiator, solution polymerization was performed at 105°C to 110°C while dropping a solution composed of 6.6 parts by mass of RHMA, 45.9 parts by mass of MAA, and 4.05 parts by mass of St over 180 minutes, and aging was performed over 100 minutes.

[0313] To the obtained polymerization solution, a solution composed of 1.20 parts by mass of toluene and 0.0750 parts by mass of stearyl phosphate as a catalyst for the cyclization condensation reaction (cyclization catalyst) was added, and a cyclization condensation reaction for forming a lactone ring structure was performed at about 90°C to 110°C under reflux for 1.5 hours.

[0314] Then, the obtained polymerization solution was passed through a multi-tube heat exchanger maintained at 220°C to complete the cyclization condensation reaction, and was introduced into a vent-type twin-screw extruder (L / D = 52) equipped with a polymer filter (filtering accuracy 5 μm) of the vane disc type at the front end at a treatment speed of 90 parts by mass / hour in terms of the amount of resin, and devolatilization of the polymerization solution was performed. The vent-type twin-screw extruder used had one rear vent and four front vents (referred to as the first vent, the second vent, the third vent, and the fourth vent from the upstream side), and the cylinder temperature was 220°C, and the degree of reduced pressure was set to 13.3 to 400 hPa (10 to 300 mmHg). During devolatilization, ion exchange water was introduced from the rear of the first vent, the second vent, and the third vent at an introduction speed of 1.3 parts by mass / hour.

[0315] The weight average molecular weight of the obtained thermoplastic acrylic resin C was 102,000, Mw / Mn was 2.3, the glass transition temperature was 125°C, the Vicat softening temperature was 116°C, and the proportions of the MMA units, the styrene units, the lactone ring structure, and the RHMA units in the copolymer were 76.8 mass%, 4.6 mass%, 16.9 mass%, and 1.7 mass%, respectively.

[0316] (Production Example 4: Thermoplastic Acrylic Resin D)

[0317] A monomer composition composed of 75.09 parts by mass of MMA, 26.04 parts by mass of styrene, and 0.46 parts by mass of t-amylperoxy 2-ethylhexanoate as a polymerization initiator was continuously supplied at 1 kg / hour to a 10 L complete mixing tank equipped with a helical ribbon impeller, and continuous polymerization was performed at an average residence time of 2.5 hours and a polymerization temperature of 150°C. The liquid surface of the polymerization tank was continuously drawn from the bottom to a prescribed level, and devolatilization was performed in a concentration device composed of a tubular heat exchanger and a vaporization tank. The degree of vacuum of the vaporization tank was 10 to 15 Torr. The resin flowing from the vaporization tank was discharged with a screw pump, extruded from a die, and after water cooling, pelletized, and introduced into a desolventizing device, and a methyl methacrylate-styrene copolymer in pellet form was obtained.

[0318] The copolymer was dissolved in methyl isobutyrate to prepare a 10 mass% methyl isobutyrate solution. Into a 1000 mL autoclave apparatus, 500 parts by mass of the 10 mass% methyl isobutyrate solution of the copolymer, 1 part by mass of 10 mass% Pd / C as a hydrogenation catalyst were charged, and the aromatic double bonds in the styrene sites of the copolymer were hydrogenated at 9 MPa of hydrogen pressure, 200°C for 15 hours. The hydrogenation catalyst was removed by a filter, and 0.04 parts by mass of Rikemal H-100 was added to the polymer solution and mixed, and then supplied to a concentration device composed of a tubular heat exchanger and a vaporization tank to perform devolatilization. The vacuum degree of the vaporization tank was 10 to 15 Torr. The resin flowing from the vaporization tank was discharged with a gear pump, extruded from a bushing die, and after water cooling, pelletized to obtain a thermoplastic acrylic resin D.

[0319] The composition of the obtained pellets was confirmed, and as a result, the structural units from each of the monomers of MMA, vinylcyclohexane in the copolymer were 73.2 mass%, 26.8 mass%, respectively. In addition, the weight average molecular weight was 148,000, Mw / Mn was 2.0, the glass transition temperature was 118°C, and the Vicat softening temperature was 112°C.

[0320] The measurement and evaluation methods of each layer film-formed in the examples and comparative examples were as follows.

[0321] [Refractive index]

[0322] The refractive index at a wavelength of 500 nm of each layer film-formed in the examples and comparative examples was obtained by a spectroscopic reflectance method after performing a spectroscopic reflectance measurement using an ultraviolet-visible near-infrared spectrophotometer (Hitachi High-Tech Corporation, UH4150) after film-forming in a single layer on a glass substrate (optical glass B270i) under the same film-forming conditions in advance.

[0323] [Thickness (film thickness) of each layer]

[0324] The thickness (film thickness) of each layer film-formed in the examples and comparative examples was obtained using a spectroscopic ellipsometer (HORIBA Ltd., UVISEL2). Note that the film thickness was calculated using the data of a sample film-formed in a single layer on a glass substrate (optical glass B270i) under the same film-forming conditions in advance.

[0325] [Example 1]

[0326] (Molding of lens)

[0327] An injection molding was performed using the thermoplastic acrylic resin A obtained in Production Example 1 using an injection molding machine (S-2000i50B manufactured by FANUC CORPORATION) to obtain a plano-convex lens molded product (lens main body) having a thickness of 3.2 mm in the optical axis direction and an effective diameter of φ 41 mm. As the finished product, in the face including the optical axis, one face was aspherical having a curvature radius R of 93.5 mm, a conic constant k of -1.12452, and no constant of even order was set. In addition, in the face including the optical axis, the other face was planar having a curvature radius of ∞.

[0328] The barrel temperature was set to Tg+135°C of the thermoplastic acrylic resin A used, and the mold temperature was set to Tg-15°C of the thermoplastic acrylic resin A used. As for the holding pressure, 4 seconds at 60 MPa was set in the first stage, and then, in order to relax the stress and strain in the inside of the molded product, 3 seconds at 40 MPa was set in the second stage. In addition, the injection speed was set to 10 mm / s.

[0329] (Film formation of primer layer and optical functional layer)

[0330] On the planar side of the above lens molded product, film formation of the primer layer and the antireflection layer as the optical functional layer was performed by a vacuum evaporation method using a vacuum evaporation device (SAPIOS GC-1300 manufactured by SHOWA CAN VACUUM CO., LTD.). Note that the electron gun (EB source G-12100 for vacuum film formation manufactured by Plasmatech company) did not have a reflection electron trap attached.

[0331] First, pre-melting of the fusible material among the evaporation materials of the antireflection layer was performed. While the vacuum tank of the vacuum evaporation device was being evacuated, Ti3O5 particles filled in the copper liner were heated with the electron gun to be melted. At this time, as shown in FIG. 2, the electron gun was set to a power of 2.5 kW, a beam current of 1.5 A, and a beam diameter of 5 mm. Figure 4corresponding to the EB output and the time so that the total energy of the EB (output power x time) becomes 340 kJ. Specifically, the EB output is linearly increased from 0 kW to 4.0 kW for 20 seconds (up to 20 seconds after the start) from the start of the pre-melting (the start of the EB irradiation), and then 4.0 kW is continued for 20 seconds (from 20 seconds after the start to 40 seconds after the start), and then linearly increased from 4.0 kW to 4.5 kW for 5 seconds (from 40 seconds after the start to 45 seconds after the start), and then 4.5 kW is continued for 20 seconds (from 45 seconds after the start to 65 seconds after the start), and then linearly increased from 4.5 kW to 5.0 kW for 2 seconds (from 65 seconds after the start to 67 seconds after the start), and then 5.0 kW is continued for 20 seconds (from 67 seconds after the start to 87 seconds after the start) to end the pre-melting. Note that the shutter was always closed, and the lens-shaped product was not provided in the evaporation device.

[0332] Then, the lens-shaped product was provided in the vacuum evaporation device, and the inside of the vacuum tank was evacuated to 1.5 x 10 -3 Pa. Then, the SiO particles filled in the molybdenum boat were heated by the resistance heating method to sublimate to perform the film formation of the undercoat layer in such a manner that the film thickness becomes 320 nm. Note that in the film formation, as the reaction gas, oxygen was introduced to make the total pressure 1.4 x 10 -2 Pa, and the film formation was performed particularly without heating the film formation target (lens-shaped product). In addition, in the film formation of the undercoat layer, the pre-melting of the evaporation material used in the film formation of the antireflection layer of the subsequent process was not performed.

[0333] Then, the Ti3O5 material which had been initially subjected to the pre-melting was re-heated, re-melted, and vaporized by the electron gun to perform the film formation of the TiO2 layer as the high refractive index layer by the electron beam evaporation method. Note that in the film formation, as the reaction gas, oxygen was introduced to make the total pressure 1.3 x 10 -2 Pa, and the film formation was performed particularly without heating the film formation target (lens-shaped product + undercoat layer). In addition, the electron beam heating of the Ti3O5 as the evaporation material was started in a state where the shutter was closed, and the film formation was performed after the re-pre-melting of the evaporation material was performed with the shutter opened. At this time, the re-pre-melting was performed in the same manner as the pre-melting. Figure 4The pre-melting was performed in such a manner that a program corresponding to the EB output and time was prepared and the pre-melting was performed in a manner that the total EB energy (output power x time) became 86 kJ. Specifically, from the start of the pre-melting (the start of the EB irradiation), the EB output was linearly increased from 0 kW to 2.5 kW for 10 seconds (until 10 seconds after the start), then 2.5 kW was continued for 5 seconds (from 10 seconds after the start to 15 seconds after the start), then 2.5 kW was linearly increased to 2.8 kW for 2 seconds (from 15 seconds after the start to 17 seconds after the start), then 2.8 kW was continued for 6 seconds (from 17 seconds after the start to 23 seconds after the start), then 2.8 kW was linearly increased to 3.3 kW for 2 seconds (from 23 seconds after the start to 25 seconds after the start), then 3.3 kW was continued for 10 seconds (from 25 seconds after the start to 35 seconds after the start), and the pre-melting was ended.

[0334] Then, the SiO2 layer as a low refractive index layer was formed by the electron beam evaporation method by heating the SiO2 particles filled in the copper inner liner with the electron gun to sublimate. Note that, in the film formation, as a reaction gas, oxygen was introduced so that the total pressure became 1.3 x 10 -2 Pa, and the film formation was performed on the film formation object (lens molding product + primer layer + TiO2 layer) without heating in particular. In addition, the electron beam heating of SiO2 as the evaporation material was started in a state where the shutter was closed, and after the pre-melting of the evaporation material was performed, the shutter was opened and the film formation was performed. At this time, the pre-melting was performed in such a manner that a program corresponding to the EB output and time was prepared and the pre-melting was performed in a manner that the total EB energy (output power x time) became 22 kJ.

[0335] The film formation of the anti-reflection layer of the structure shown in Table 1 was performed by alternately repeating the film formation of the above-described TiO2 layer and SiO2 layer three times, and a plastic lens was obtained. Note that, before and during the film formation of the TiO2 layer, the pre-melting of the evaporation material used in the film formation of the SiO2 layer of the subsequent process was not performed, and similarly, before and during the film formation of the SiO2 layer, the pre-melting of the evaporation material used in the film formation of the TiO2 layer of the subsequent process was not performed.

[0336] [Example 2]

[0337] As the thermoplastic acrylic resin, thermoplastic acrylic resin B was used instead of thermoplastic acrylic resin A, and otherwise, the same as in Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0338] [Example 3]

[0339] As the thermoplastic acrylic resin, thermoplastic acrylic resin C was used instead of thermoplastic acrylic resin A, and otherwise, the same as in Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0340] [Example 4]

[0341] As the thermoplastic acrylic resin, thermoplastic acrylic resin D was used instead of thermoplastic acrylic resin A, and otherwise, similarly to Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0342] [Example 5]

[0343] Except that the film formation of the primer layer was performed so that the film thickness became 450 nm, similarly to Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0344] [Example 6]

[0345] Except that the film formation of the primer layer was performed so that the film thickness became 610 nm, similarly to Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0346] [Example 7]

[0347] Except that the film formation of the primer layer was performed so that the film thickness became 900 nm, similarly to Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0348] [Example 8]

[0349] The film formation of the primer layer was performed so that the film thickness became 100 nm, and further, as the electron gun for heating the evaporation material, an electron gun attached with a reflection electron trap was used, and otherwise, similarly to Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0350] [Example 9]

[0351] The film formation of the primer layer was performed so that the film thickness became 100 nm, and further, the re-pre-melting of the pre-melted Ti3O5 material was performed so that the EB total energy (output power x time) became 640 kJ, and further, as the electron gun for heating the evaporation material, an electron gun attached with a reflection electron trap was used, and otherwise, similarly to Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0352] [Example 10]

[0353] The re-pre-melting of the pre-melted Ti3O5 material was performed so that the EB total energy (output power x time) became 640 kJ, and further, as the electron gun for heating the evaporation material, an electron gun attached with a reflection electron trap was used, and otherwise, similarly to Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0354] [Example 11]

[0355] In the film formation of the primer layer, oxygen was introduced to make the total pressure 8.0 x 10 -3 Pa, and otherwise, the same as Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0356] [Example 12]

[0357] Except that the preliminary pre-melting of the Ti3O5 particles before the film formation of the primer layer was performed in such a manner that the total EB energy (output power x time) became 640 kJ, and otherwise, the same as Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced. Note that the above pre-melting was performed according to the procedure of (c), specifically, the EB output was linearly increased from 0 kW to 3.5 kW for 15 seconds (until 15 seconds after the start), and then 3.5 kW was continued for 5 seconds (from 15 seconds after the start to 20 seconds after the start), and then linearly increased from 3.5 kW to 7.0 kW for 5 seconds (from 20 seconds after the start to 25 seconds after the start), and then 7.0 kW was continued for 15 seconds (from 25 seconds after the start to 40 seconds after the start), and then linearly decreased from 7.0 kW to 6.1 kW for 15 seconds (from 40 seconds after the start to 55 seconds after the start), and then 6.1 kW was continued for 60 seconds (from 55 seconds after the start to 115 seconds after the start) to end the pre-melting. Figure 4

[0358] [Example 13]

[0359] The film formation of the partial reflection layer was performed as the optical functional layer, and otherwise, the same as Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0360] [Example 14]

[0361] The preliminary pre-melting of the Ti3O5 particles before the film formation of the primer layer was performed in the state where the lens molding product was set in the evaporation device, and in addition, an electron gun attached with a reflection electron trap was used as the electron gun for heating of the evaporation material, and otherwise, the same as Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0362] [Example 15]

[0363] As the thermoplastic acrylic resin, thermoplastic acrylic resin B was used instead of thermoplastic acrylic resin A, and otherwise, the same as Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0364] [Example 16]

[0365] ​As the thermoplastic acrylic resin, thermoplastic acrylic resin C was used instead of thermoplastic acrylic resin A, and otherwise, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0366] [Example 17]

[0367] As the thermoplastic acrylic resin, thermoplastic acrylic resin D was used instead of thermoplastic acrylic resin A, and otherwise, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0368] [Example 18]

[0369] Except that the film formation of the primer layer was performed so that the film thickness became 450 nm, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0370] [Example 19]

[0371] Except that the film formation of the primer layer was performed so that the film thickness became 610 nm, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0372] [Example 20]

[0373] Except that the film formation of the primer layer was performed so that the film thickness became 900 nm, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0374] [Example 21]

[0375] Except that the film formation of the primer layer was performed so that the film thickness became 100 nm, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0376] [Example 22]

[0377] Except that the film formation of the primer layer was performed so that the film thickness became 100 nm, and that the re-pre-melting of the pre-melted Ti3O5 material was performed so that the EB total energy (output power x time) became 640 kJ, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0378] [Example 23]

[0379] Except that the re-pre-melting of the pre-melted Ti3O5 material was performed so that the EB total energy (output power x time) became 640 kJ, in the same manner as in Example 14, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0380] [Example 24]

[0381] At the time of film formation of the undercoat layer, oxygen was introduced so that the total pressure became 8.0 x 10 -3 Pa, and otherwise, in the same manner as in Example 14, a plastic lens provided with an undercoat layer and an optical functional layer was produced.

[0382] [Example 25]

[0383] The primary pre-melting of the Ti3O5 particles before film formation of the undercoat layer was performed in such a manner that the total EB energy (output power x time) became 640 kJ, and otherwise, in the same manner as in Example 14, a plastic lens provided with an undercoat layer and an optical functional layer was produced. Note that the above pre-melting was performed in accordance with the procedure of (c), specifically, the EB output was linearly increased from 0 kW to 3.5 kW for 15 seconds (until 15 seconds after the start), and then 3.5 kW was continued for 5 seconds (from 15 seconds after the start to 20 seconds after the start), and then linearly increased from 3.5 kW to 7.0 kW for 5 seconds (from 20 seconds after the start to 25 seconds after the start), and then 7.0 kW was continued for 15 seconds (from 25 seconds after the start to 40 seconds after the start), and then linearly decreased from 7.0 kW to 6.1 kW for 15 seconds (from 40 seconds after the start to 55 seconds after the start), and then 6.1 kW was continued for 60 seconds (from 55 seconds after the start to 115 seconds after the start) to end the pre-melting. Figure 4

[0384] [Example 26]

[0385] Film formation of a partial reflection layer was performed as the optical functional layer, and otherwise, in the same manner as in Example 14, a plastic lens provided with an undercoat layer and an optical functional layer was produced.

[0386] [Comparative Example 1]

[0387] At the time of film formation of the undercoat layer, oxygen was introduced so that the total pressure became 3.5 x 10 -2 Pa, and otherwise, in the same manner as in Example 1, a plastic lens provided with an undercoat layer and an optical functional layer was produced.

[0388] [Comparative Example 2]

[0389] The primary pre-melting of the Ti3O5 particles before film formation of the undercoat layer was performed in the state where the lens molding product was set in the evaporation device, and in addition, the pre-melting at this time was performed in such a manner that the total EB energy (output power x time) became 86 kJ, and otherwise, in the same manner as in Example 1, a plastic lens provided with an undercoat layer and an optical functional layer was produced. Note that the above pre-melting was performed in accordance with the procedure of (c), specifically, the EB output was linearly increased from 0 kW to 3.5 kW for 15 seconds (until 15 seconds after the start), and then 3.5 kW was continued for 5 seconds (from 15 seconds after the start to 20 seconds after the start), and then linearly increased from 3.5 kW to 7.0 kW for 5 seconds (from 20 seconds after the start to 25 seconds after the start), and then 7.0 kW was continued for 15 seconds (from 25 seconds after the start to 40 seconds after the start), and then linearly decreased from 7.0 kW to 6.1 kW for 15 seconds (from 40 seconds after the start to 55 seconds after the start), and then 6.1 kW was continued for 60 seconds (from 55 seconds after the start to 115 seconds after the start) to end the pre-melting. Figure 4 ​The procedure of (b) was carried out, specifically, the EB output was linearly increased from 0 kW to 2.5 kW for 10 seconds (up to 10 seconds after the start) and then 2.5 kW was continued for 5 seconds (from 10 seconds after the start to 15 seconds after the start) and then linearly increased from 2.5 kW to 2.8 kW for 2 seconds (from 15 seconds after the start to 17 seconds after the start) and then 2.8 kW was continued for 6 seconds (from 17 seconds after the start to 23 seconds after the start) and then linearly increased from 2.8 kW to 3.3 kW for 2 seconds (from 23 seconds after the start to 25 seconds after the start) and then 3.3 kW was continued for 10 seconds (from 25 seconds after the start to 35 seconds after the start) to end the pre-melting.

[0390] [Comparative Example 3]

[0391] The film formation of the primer layer was carried out so that the film thickness became 100 nm, and otherwise, the same as in Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0392] [Comparative Example 4]

[0393] The film formation of the primer layer was carried out so that the film thickness became 20 nm, and otherwise, the same as in Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0394] [Comparative Example 5]

[0395] The film formation of the primer layer was carried out so that the film thickness became 20 nm, and otherwise, the same as in Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0396] [Comparative Example 6]

[0397] During the film formation of the primer layer, oxygen was introduced so that the total pressure became 3.5 x 10 -2 Pa, and otherwise, the same as in Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0398] [Comparative Example 7]

[0399] A thermoplastic acrylic resin (Asahi Kasei Corporation, DELPET 80N, Vicat softening temperature 109°C) having low heat resistance was used instead of the thermoplastic acrylic resin A, and otherwise, the same as in Example 1, a plastic lens provided with a primer layer and an optical functional layer was produced.

[0400] [Comparative Example 8]

[0401] At the time of forming the primer layer, oxygen was introduced so that the total pressure became 3.5 x 10 -2 A plastic lens provided with a primer layer and an optical functional layer was produced in the same manner as in Example 14, except that the primer layer was formed in such a manner that the film thickness became 20 nm.

[0402] [Comparative Example 9]

[0403] A plastic lens provided with a primer layer and an optical functional layer was produced in the same manner as in Example 14, except that the primer layer was formed in such a manner that the film thickness became 20 nm.

[0404] [Comparative Example 10]

[0405] At the time of forming the primer layer, oxygen was introduced so that the total pressure became 3.5 x 10 -2 A plastic lens provided with a primer layer and an optical functional layer was produced in the same manner as in Example 14, except that the primer layer was formed in such a manner that the film thickness became 20 nm.

[0406] [Comparative Example 11]

[0407] A plastic lens provided with a primer layer and an optical functional layer was produced in the same manner as in Example 14, except that a thermoplastic acrylic resin (Asahi Kasei Co., Ltd., DELPET 80N, Vicat softening temperature 109°C) having low heat resistance was used instead of the thermoplastic acrylic resin A.

[0408] The measurement and evaluation method of the plastic lenses produced in the Examples and Comparative Examples were as follows.

[0409] (Durability Evaluation)

[0410] (1) Initial Adhesion

[0411] In order to evaluate the adhesion of the coating of the plastic lenses obtained by the Examples and Comparative Examples, a grid test was performed in accordance with JIS K 5600-5-6. A 25 grid of 1 mm x 1 mm was made on the planar side of the plastic lens using a multi-blade cutting tool, a transparent tape (NICHIBAN CO., LTD. "LP-24") was attached to the grid, and after the tape was peeled off at once, the state of the surface of the grid portion was observed with respect to whether or not the film (primer layer and optical functional layer) was peeled off. The results were classified as follows, and classification 0 or 1 was set as A (good), classification 2 was set as B (practical), and classifications 3 to 5 were set as C (poor).

[0412] (Classification)

[0413] 0: The edges of the cuts were completely smooth, and none of the grids were peeled off.

[0414] 1: There is slight peeling of the film at the intersection of the cuts. The proportion of the grid portion peeled is not more than 5% of the total area of the grid portion.

[0415] 2: There is slight peeling of the film along the edges of the cuts and / or at the intersections. The proportion of the grid portion peeled is more than 5% but not more than 15% of the total area of the grid portion.

[0416] 3: There is partial or complete peeling of the film along the edges of the cuts and / or at several grid portions. The proportion of the grid portion peeled is more than 15% but not more than 35% of the total area of the grid portion.

[0417] 4: There is partial or complete peeling of the film along the edges of the cuts and / or at several grid portions. The proportion of the grid portion peeled is more than 35% but not more than 65% of the total area of the grid portion.

[0418] 5: Any case of peeling that cannot be classified even as classification 4.

[0419] (2) Humidity heat test

[0420] A humidity heat test was performed using the plastic lenses obtained in the Examples and Comparative Examples. The plastic lenses were put into a constant temperature and humidity chamber (PL-4KP manufactured by ESPEC CORP) set at 85°C, 85% RH, and left for 200 hours in an environment of 85°C, 85% RH. Then, the plastic lenses were taken out of the constant temperature and humidity chamber and left for 24 hours in a constant temperature room of 23°C, 50% RH.

[0421] (2-1) Appearance change after humidity heat test

[0422] In the plastic lenses after the end of the humidity heat test, visual observation of the lens surface was performed, and the presence or absence of the generation of cracks was determined.

[0423] (2-2) Adhesion after humidity heat test

[0424] In the plastic lenses after the end of the humidity heat test, adhesion evaluation of the film (base coat layer and optical functional layer) was performed using the same evaluation method as the initial adhesion of (1).

[0425] The results of each measurement and evaluation are shown in Tables 1 and 2.

[0426]

[0427]

[0428] The plastic lens of the present application is excellent in productivity and has extremely good durability. Therefore, the plastic lens of the present application can be applied to lenses and the like for use in household articles, OA equipment, AV equipment, components for battery electric equipment, lighting equipment, automobile components, and the like.

[0429] As the lens in household articles, OA equipment, AV equipment, components for battery electric equipment, lighting equipment, and the like, for example, there can be mentioned lenses for cameras of smartphones or tablet computers; lenses used in telescopic cameras (periscopic cameras) of folded optics; lenses used in VR (virtual reality) / AR (augmented reality) / MR (mixed reality) / SR (substitute reality) / DR (disappearance reality) / XR (cross reality) head-mounted displays, liquid crystal projectors, near-infrared sensors (LiDAR), and the like, particularly, small thin-walled optical lenses of uneven shape; lenses for optical communication; lenses, Fresnel lenses, phase plates provided with a micro-lens array, and the like.

[0430] As the lens in automobile components and the like, there can be mentioned lenses used in head-up displays; camera lenses for vehicles (particularly, front lenses), and the like.

[0431] In addition, there can be mentioned lenses used in floating displays, for example, base materials of retro-reflective sheets or partially transmissive mirrors; micro-lens arrays for constituting a dihedral angle reflector array; lenses for enlarging, reducing, or correcting an image plane or aberration, and the like.

Claims

1. A method for producing a plastic lens, comprising the steps of sequentially forming a primer layer and an optical functional layer on at least one surface of a lens body made of resin, wherein: The lens body is made of a thermoplastic acrylic resin having a glass transition temperature of 116°C or higher. The undercoat layer is formed by a resistance heating type vacuum evaporation method, SiO is used as the evaporation material of the undercoat layer, and the amount of oxygen is controlled to be less than 3.0×10 -2 Pa pressure formation, The optical function layer is formed by an electron beam heating type vacuum evaporation method, and the evaporation material of the optical function layer is pre-melted before and after the formation of the primer layer.

2. The method for manufacturing a plastic lens according to claim 1, wherein: The pre-melting before forming the primer layer is performed in a state where the lens is not placed in a vapor deposition device.

3. The method for manufacturing a plastic lens according to claim 2, wherein: After forming the primer layer, pre-melting of the fusible material in the vapor deposition material of the optical function layer is performed so that the total electron beam energy is less than 1500 kJ, where the total electron beam energy is a value obtained by multiplying the output by the time.

4. The method for manufacturing a plastic lens according to claim 3, wherein: The thickness of the undercoat layer is 200 nm or more and less than 1000 nm.

5. The method for manufacturing a plastic lens according to claim 3, wherein: The thickness of the primer layer is greater than 80 nm and less than 1000 nm. After the primer layer is formed, a reflection electron trap is attached to the electron gun used.

6. The method for manufacturing a plastic lens according to claim 1, wherein: The lens is placed in a vapor deposition apparatus and pre-melting is performed before forming the primer layer.

7. The method for manufacturing a plastic lens according to claim 6, wherein: Before and after forming the primer layer, pre-melting of the fusible material in the vapor deposition material of the optical function layer is performed so that the total electron beam energy is less than 1500 kJ. The total electron beam energy is a value obtained by multiplying the output by time.

8. The method for manufacturing a plastic lens according to claim 7, wherein: The thickness of the primer layer is greater than 200 nm and less than 1000 nm. Before forming the primer layer, a reflection electron trap is attached to the electron gun used.

9. The method for manufacturing a plastic lens according to claim 7, wherein: The thickness of the primer layer is greater than 80 nm and less than 1000 nm. Before and after forming the primer layer, the electron guns used were each equipped with a reflection electron trap.

10. The method for producing a plastic lens according to any one of claims 1 to 9, wherein: The optical functional layer is any one of an anti-reflection layer, a partial reflection layer, and a high reflection mirror.

11. The method for manufacturing a plastic lens according to claim 10, wherein: The forming of the optical function layer includes a step of setting the surface temperature of the lens body to 60° C. or higher.

12. The method for manufacturing a plastic lens according to claim 11, wherein: The vapor deposition material pre-melted before forming the primer layer is not processed but directly used in the pre-melting after forming the primer layer. After the pre-melting after forming the primer layer is completed, the vapor deposition process of the optical functional layer is carried out.

Citation Information

Patent Citations

  • Antireflection film of optical parts made of synthetic resin

    JP1994273601A

  • Near-eye display optical module

    JP2017021321A

  • Imidized acrylic polymers

    US4246374A

  • Wide-angle collimating optical device

    US6563638B2

  • Plastic lens, lens unit and method for producing plastic lens

    WO2023074597A1